Melatonin inhibits ethylene biosynthesis by regulating MdERF1/MdERF3 pathway during apple fruit ripening - Chen Li; Qian Yu; Yanmin Du; Wenhui Wang; Yajing Si; Yuling Liang; Shijiao Lin; Guangxin Yang; Weiting Liu; Aide Wang; Yinglin Ji (Postharvest Biology and Technology, 2026)

Colletotrichum aotearoa B. Weir & P.R. Johnst causing leaf anthracnose in Lithocarpus litseifolius in China - Yuling Wang; Chang Liu; Guolin Cai; Ning Shu; Ziqiang Luo; Zixuan Qiu; Wuping Yan (Crop Protection, 2026)

A 3D porous KCuFC/collagen fibers/gelatin adsorbent for ultra-fast cesium capture from radioactive wastewater - Xiaoxia Ye; Shanyuan Chen; Juan Liu; Yuling Tang; Jianfei Zhou; Wei Luo; Jie Chen (Bioresource Technology, 2026)

Modeling the cooling effects of urban rivers on surrounding built-up areas via a SOMUCH-based scaled outdoor experiment - Lin Liu; Xin Feng; Jian Hang; Jiajia Hua; Guanwen Chen; Qing Wu; Na Zhao; Yuguang Zhao; Yuling Yang (Sustainable Cities and Society, 2026)

Identification and functional validation of a beta-amyrin synthase for Clinopodiside A biosynthesis in medicinal plant Clinopodium chinense - Qianlan Liu; Chun Liu; Zitong Tan; Yu Fu; Ting He; Yi Yuan; Yuling Tai (Plant Science, 2026)

Small-sample BOD₅ interval prediction for aeration recommendation using conformal calibrated LightTransformer-LGBM model - Wangben Zhao; Yuling Liu; Lu Wang; Shuaishuai Li; Li Sun; Shuang Ren (Journal of Environmental Chemical Engineering, 2026)

Metabolic reprogramming for post-acidification control in fermented milk via post-sterilization treatment - Han Lu; Liru Cui; Menglu Li; Yuling Xue; Yannan He; Chang Liu; Yan Wu; Shijie Wang (Food Microbiology, 2026)

Divergent temporal dynamics of yield response to nitrogen fertilization across the three major cereals - Xiaowen Zhao; Meitong Wang; Baiheng Su; Yuling Li; Xiaohe Wang; Yu Jiang; Zhenghui Liu; Ganghua Li; Yanfeng Ding; Weiwei Li (Field Crops Research, 2026)

Consistent functional genes in methanogens along soil profiles in a temperate marshland - Yuling Tan; Nannan Wang; Kexin Li; Yunjiang Zuo; Jianzhao Liu; Ziyu Guo; Ming Yang; Wenwen Tan; Yuedong Guo; Yanyu Song; Fenghui Yuan; Xiaofeng Xu; et al. (Soil Ecology Letters, 2026)

Co-infection with CAV facilitates ALV-K replication and induces severe immunosuppression in chickens - Yuling Cui; Mengyue Dong; Zhanxin Wang; Yang Liu; Jiajia Liu; Hainuo Zeng; Runlin Shao; Ruiheng Liu; Yuanjia Liu; Qingmei Xie; Xinheng Zhang (Veterinary Microbiology, 2026)

Genome-wide characterization of the apple WOX family identifies MdWOX13 as a repressor of fruit ripening - Yinglin Ji; Shijiao Lin; Mingqian Wang; Yuling Liang; Meili Xin; Yanan Wang; Weiting Liu; Aide Wang; Bin Li (Postharvest Biology and Technology, 2026)

Multi-omics insights into key aroma compound formation during Chinese bayberry wine fermentation by Pichia kluyveri ZFM-0524 - Shuxun Liu; Mingfeng Cao; Yan Zhao; Yufeng Xu; Luan Zhang; Yuling Cai; Qing Gu (International Journal of Food Microbiology, 2026)

Using transgenic zebrafish to assess the effects of SCCPs exposure on embryonic neural development and its potential mechanisms - Jinxian Yang; Ruiyao Huang; Jin Wang; Mengna Jiang; Fengxu Wang; Yuling Jiang; Jiaxin Liu; Mingjing Sun; Sheng Chen; Tian Zhou; Xinyuan Zhao; Shunxing Zhu (Chemico-Biological Interactions, 2026)

Suitable particle-size biochar enhances resilience of potato production and soil environmental to irregular precipitation in semiarid region - Zhaoyang Li; Nan Shi; Zhimin Yang; Yubo Cao; Shimeng Fan; Musawer Abbas; Weixing Shan; Ansabayeva Assiya; Zhikuan Jia; Enke Liu; Kadambot H.M. Siddique; Ruixia Ding; et al. (Bioresource Technology, 2026)

Molecular understanding of plant pollination, fertilization, seed development and protoplast regeneration - Jiang-Guo Meng; Pu Liu; Hanxian Xiong; Wei Wang; Gang Xu; Xu Xin; Zijun Lan; Changkai Ma; Na Wang; Xuecheng Zhang; Ce Shi; Shu Chang; et al. (Science China Life Sciences, 2026)
Sexual reproduction in plants is a tightly coordinated process that underpins biodiversity, drives speciation, and serves as a foundation for modern crop improvement. Here, we synthesize recent advances in elucidating the molecular mechanisms governing major reproductive events in flowering plants, including male and female gametogenesis, pollen-pistil communication, double fertilization, embryogenesis, and endosperm-mediated seed development. We also discuss the integration of asexual propagation through protoplast regeneration, highlighting its emerging importance in plant biotechnology. Together, these insights deepen our understanding of fundamental reproductive biology and open new opportunities for the rational design of hybrid breeding systems and stress-resilient crops, with broad implications for global food security under changing climatic conditions.

Responses of soil quality, enzyme-based ecosystem multifunctionality, and maize yield to short-term straw return with shallow-buried drip irrigation in Northeast China - Chutong Liu; Shucheng Liu; Boyang Hou; Yinong Zhao; Peilong Luo; Jing An; Yuling Zhang (Plant and Soil, 2026)

Cationic Dendrimer-Directed Pore Architecture in Polyamide Membranes for Tunable Ion Separation - Bingbing Yuan; Menghan Wu; Jinmiao Cui; Lei Zhang; Zequn Liao; Ping Hu; Yuling Ren; Lihong Liu; Siheng Zhao; Meng You; Dongxiao Yang; Q. Jason Niu (Water Research, 2026)

Synergy of substrate, plant, and microorganism in constructed wetlands enhances chromogenic substances and nitrogen removal from real chemical tailwater - Yi Liu; Yuling Huang; Chunhua Li; Qiang He; Hong Li (Journal of Water Process Engineering, 2026)

Effects of defatting treatments on flavor components and lipid characteristics in bowl-steamed Tan lamb: A comprehensive investigation based on lipidomics and multi-platform flavor analysis - Wen Wang; Yufeng Duan; Xue Yang; Ruheng Shen; Mengying Liu; Xiaoqin Xi; Li Zhang; Long He; Yuling Qu; Liang Lin; Qiang Cheng (Food Chemistry, 2026)

Smart textile wearables for human-environment interaction - Yuling Chen; Junni Ren; Mingwen Zhang; Dilusha Rajapakse; Fuhao Liu; Byeong Woon Lee; Sang Min Won; Xiaoxiao Zhu (Chemical Engineering Journal, 2026)

Antibacterial mechanisms of terpinen-4-ol against Aeromonas hydrophila - Kaiqi Lian; Xiangfeng Meng; Yuhang Wang; Shengming Ma; Xiaolong Li; Ren Ren; Yuling Liu; Lingling Zhou; Renhai Peng (Archives of Microbiology, 2026)

The Identification of Digramma interrupta (Diphyllobothriidae: Ligula) in a Captive Red-Crowned Crane and a Crucian Carp Reveals a New Case for Co-Occurrence - Maolin Lu; Yuling Yang; Mengchao Zhou; Yaxian Lu; Honyan Yu; Ruisi Zhang; Tianlu Liu; Mengru Zhao; Lei Han; Zhijun Hou (Acta Parasitologica, 2026)

Long-term trends and risk regulation of heat exposure in megacities: seasonal dynamics and determinants - Ziwen Jin; Shuyi Zhang; Ke Zeng; Muyao Ma; Yue Yang; Yuling Fu; Hanxin Tang; Shan Yin; Ji Zheng; Min Liu (Environment, Development and Sustainability, 2026)

Early-rice straw return rnhances Cd accumulation in late-rice through increased soil Cd bioavailability and root uptake in a Cd-contaminated double-cropping rice system - Yuhui Zeng; Geyi Xu; Changsong Huang; Zhong Hu; Qian Qi; Yuling Liu; Xiao Deng; Yang Yang; Changjun Li; Si Luo (Journal of Environmental Sciences, 2026)

Novel inter-cable wire rope dampers for hanger cable vibration control: Experiment, FE modeling method, and Field test - Shilong Yang; Keyu Lai; Wei Fan; Yuling Liu; Zhiheng Chen; Zhengqing Chen (Engineering Structures, 2026)

Improving embryo rescue efficiency in seedless grape breeding with zeatin - Xi Chen; Shaopeng Zhao; Xinyu Chen; Mengyu Ma; Xue Wen; Yao Xiao; Yong Wang; Yuling Li; Feng Sun; Guotian Liu; Tingting Chen; Yan Xu (Protoplasma, 2026)

From importance to sensitivity: fuel consumption analysis of heavy-duty diesel vehicles - Yuling Song; Tianhao Liu; Tiezhu Li; Xiyuan Hu; Ruizhi Zhang; Haibo Chen (Transportation Research Part D: Transport and Environment, 2026)

Integrated approach for heavy metal ion adsorption and heterogeneous fenton denitrification using functionalized steel slag catalyst - Lingtao Liu; Yuan Xu; Zhi Gao; Jinbo Ouyang; Zhuyao Li; Yuling Zhu; Jianhua Ding; Feiqiang He (Journal of Environmental Management, 2026)

Characterization of gut lipases in Helicoverpa armigera: New insights into the role of intracellular lipases in cholesterol homeostasis - Zhen Yang; Haoyu Tan; Xiaoqing Yang; Yuling Zhang; Junhao Liang; Wenqing Kuang; Zhanfeng Zhang; Tong-Xian Liu; Xiangfeng Jing (Insect Biochemistry and Molecular Biology, 2026)

Ameliorative Effects of an Antioxidant and Anti-Inflammatory Limosilactobacillus fermentum TG017 on DSS-Induced Ulcerative Colitis in Mice - Qianhao Hou; Yuling Li; Zuanyuan Huang; Honghua Hu; Xin Li; Jinyuan Zhang; Wenying Duan; Songsong Pan; Zetian Wang; Xiaodong Liu; Wei Xu; Lijun Liao (Probiotics and Antimicrobial Proteins, 2026)

Transcription factor McORA activates McHDR to enhance aphid-repelling (E)-β-farnesene biosynthesis in Matricaria chamomilla L. - Honggang Wang; Jin Wang; Wenjing Cheng; Siqing Zhu; Qianlan Liu; Yuling Tai; Yi Yuan (Plant Cell Reports, 2026)

Development and Validation of An HPLC Method for Isolation and Structural Elucidation of Impurities in Chlorogenic Acid Self-Microemulsion Formulations - Yue Gao; Yanan Wang; Jing Xu; Ming Ji; Dongyang Zhao; Yanqi Han; Longhui Hao; Yi Zhang; Ying Sun; Zhenshuai Qin; Jun Ye; Hongliang Wang; et al. (Journal of Pharmaceutical Innovation, 2026)

The pulse of ancient fires: Reconstructing Toarcian wildfire regimes from fossil charcoals in northwest China - Yuling Na; Xiao Shi; Chi Tian; Wenpei Pei; Qianqian Song; Shaoting Tian; Bing Wang; Yan Liu; Leon Nahuel Torres; Jianxin Yu (Review of Palaeobotany and Palynology, 2026)

Understanding the tradeoff between the flood risk and the hydropower benefit from the integrated flood control operation of a reservoir group and a flood detention basin - Zhenyu Mu; Dedi Liu; Zhenyu Wang; Yuling Zhang; Pan Liu; Lihua Xiong; Jie Chen; Hua Chen; Jiabo Yin (Journal of Hydrology, 2026)

A novel vacuum steam – Microwave thawing of frozen pork - Fangran Liu; Weidong Wu; Hua Zhang; Yuyao Sun; Yuling Liu (Journal of Food Engineering, 2026)

l-Lysine effects on myosin carbonylation in metal-catalyzed oxidation: Implications for thermal gelation - Yuling Liu; Yuqi Wu; Ge Han; Jiaxin He; Yawen Wang; Jinfeng Pan; Shengjie Li (Food Research International, 2026)

Metagenomic and metabolomic insights into microbial-metabolite interactions underlying flavor formation in Hebei-style soybean paste fermentation - Chang Liu; Jingjing Hao; Han Lu; Pingping Ma; Yannan He; Yuling Xue; Zhiyuan Kang; Shijie Wang (Food Research International, 2026)

A two-wave panel biomonitoring study of changes in urinary pesticide metabolites and their associations with liver function and inflammatory markers - Dandan Liu; Xiaotong Li; Yuling Chen; Fenfang Deng; Jia He; Chongshan Guo; Jun Yuan; Lei Tan (Environmental Research, 2026)

Characteristics and source apportionment of atmospheric fine particulate-bound mercury (PBM2.5) in abandoned mercury mining areas in southwestern China - Yuling Kuang; Longchao Liang; Shasha Liu; Xian Dong; Fang Zhu; Xiaohang Xu; Zhuo Chen; Yayun Li; Yaji Li; Guangle Qiu (Acta Geochimica, 2026)

Mercury dynamics and speciation in paddy soils irrigated with acid mine drainage from abandoned coal mine: Insights from vertical profiling - Shasha Liu; Longchao Liang; Xiaohang Xu; Yuling Kuang; Le Wang; Guangle Qiu; Zhuo Chen; Xian Dong; Jialiang Han (Acta Geochimica, 2026)

Breaking acidification-ammonia inhibition cycle in anaerobic co-digestion with alkaline lime mud via synthetic microbial consortium - Linpei Liu; Yao Ren; Xiaoru Chen; Jun Wang; Yuling Huang; Pan Zhang; Qili Zhu; Han Qin; Furong Tan; Mingxiong He; Yong Zhuang (Journal of Environmental Chemical Engineering, 2026)

Deep fertilization effects on potato production and GHG emissions depend on soil C:N:P-enzyme interactions: Evidence from a 4-year study - Zhaoyang Li; Nan Shi; Yixuan Yuan; Haiyang Chang; Yuling Meng; Weixing Shan; Moskvicheva Elena; Ansabayeva Assiya; Zhikuan Jia; Xiaolong Ren; Kadambot H.M. Siddique; Ruixia Ding; et al. (European Journal of Agronomy, 2026)

Cellulose-based ultralight foam with dual-scale porosity from hybrid fibers for sustainable oil-water separation - Weiqiang Li; Jingge Liu; Meiying Li; Haitao Lin; Jian Fang; Xiaoqiao Wang; Jianchu Xu; Yuling Li; Junze Zhang; Xinheng Li; Gang Li (Carbohydrate Polymers, 2026)

A decision support system for coagulant dosage using explainable NSGA-II optimized stacking framework - Wangben Zhao; Yuling Liu; Lu Wang; Shuaishuai Li; Li Sun; Ren Shuang (Journal of Water Process Engineering, 2026)

Assessing the variations of the available flood storage capacity in a flood retention basin due to the changing environment - Yuling Zhang; Dedi Liu; Zhenyu Wang; Zhenyu Mu; Jiaoyang Wang; Pan Liu; Lihua Xiong; Jie Chen; Hua Chen (Journal of Environmental Management, 2026)

Adjusting fertilization depth for sustainable potato production in arid and semi-arid regions - Zhaoyang Li; Yukang Wang; Nan Shi; Yixuan Yuan; Lianjun Wei; Weixing Shan; Medelbek Meruyert; Ansabayeva Assiya; Zhikuan Jia; Kadambot H.M. Siddique; Ruixia Ding; Peng Wu; et al. (Field Crops Research, 2026)

Multistimuli-responsive degradable metal-organic framework nanoplatform potentiates photoimmunotherapy for hepatocellular carcinoma via cGAS-STING pathway activation - Yahui Wu; Zhipu Liu; Yi Zhang; Senfeng Zhao; Miaoqing Li; Ruiyang Zhang; Jiahui Cao; Peng Liu; Liming Song; Yin Liu; Yunpeng Zhai; Weijie Wang; et al. (Chemical Engineering Journal, 2026)

Epicoccum sorghinum as a leaf spot disease-causing pathogen in Lithocarpus litseifolius in China - Yuling Wang; Meng Li; Changjiang Liu; Guolin Cai; Mengxing Wang; Wuping Yan; Jianfeng Chen (Crop Protection, 2026)

Adsorptive Removal of Ibuprofen from Aqueous Solution by UiO-66: Performance Evaluation and Mechanistic Insights - Luo Xinzeng; Liu Yuling; Wang Zhuoran; Rong Wang; Hao Shu; Hongli Wang (Water, Air, & Soil Pollution, 2026)

Molecular Dissection of Response Mechanism and Leaf Color Variation in Ulmus Pumila Cv.‘Jinye’ Under Saline-Alkali Stress - Shufang Yan; Yichao Liu; Shuxiang Feng; Gongdan Zhou; Yuling Li; Yinran Huang (Journal of Crop Health, 2026)

Comammox Nitrospira dominates autotrophic nitrification in paddy fields under long-term fertilization - Bingjie Ren; Yanping Wang; Yuchao Wang; Yuling Yang; Zhenfa Su; Haikun Wu; Wangting Yang; Yuhan Jin; Jinghao Jin; Shuai Liu; Lidong Shen; Xu Zhao (Agriculture, Ecosystems & Environment, 2026)

Interpretable machine learning model based on floc images for monitoring the coagulation process - Shuaishuai Li; Yuling Liu; Zhixiao Wang; Peng Guo; Chuanchuan Dou; Wangben Zhao (Process Safety and Environmental Protection, 2026)

Development and simulation-based optimization of a Split-flow low-aerobic/anoxic/Oxic process integrating partial nitrification -denitrification with step feeding for enhanced nitrogen removal - Li Sun; Yuling Liu; Hao Shu; Yaohui Shao; Zhiqiang Xu; Jiayu Qi (Journal of Water Process Engineering, 2026)

Recent heat wave across the Yunnan-Guizhou plateau and its impact on alpine lakes - Jiabin Peng; Junxu Chen; Xiaohui Pan; Yuling Luo; Siqi Feng; Tie Liu; Xi Chen (Journal of Cleaner Production, 2026)

Physicochemical properties, microbial diversity, metabolites and their potential relationships of traditional Chinese Zhacai fermented for different periods - Xinyi Wang; Yuanli Luo; Yuanqing Gu; Ting Ren; Yuling Liu; Xinhui Wang; Nan Zhao; Xin Nie; Dayu Liu; Zhiping Zhao (International Journal of Food Microbiology, 2026)

Constructing amorphous CoP/Vs-Ni3S2 p-n junction with enhanced interface built-in electric field: A strategy for stable and high-performance overall water splitting catalysis - Zhiwei Liu; Aize Hao; Rongxing He; Niandan Zhao; Yuling Ye; Xiaonan Liu (Chemical Engineering Journal, 2026)

An epoxy-based composite coating with CoFeNi/N-doped carbon for integrated flame retardancy, photothermal conversion, and microwave absorption in thermal management - Biyu Huang; Yuling Wang; Yusheng Tong; Jie Shen; Haopeng Zhang; Lei Liu; Meng Liu; Shaoxiang Li; Chuanmei Jiao; Xilei Chen (Chemical Engineering Journal, 2026)

Anticancer Activity of Endophytic Bacterial Extracts from Potentilla supina in HepG2 and HCT116 Cells - Xia Li; Xinxin Zhao; Jinqiu Gui; Yuling Liu; Guiru Kong (Current Microbiology, 2026)

SFG enhances apoptosis of hepatocellular carcinoma by inhibiting tunneling nanotubes-mediated mitochondrial transport in the tumor microenvironment - Shasha Kong; Yuling Liu; Ruying Tang; Hui Li; Hongmei Lin; Longfei Lin (Apoptosis, 2026)

Revealing the spatial distribution of crown base height across China based on close-range Lidar data - Zekun Yang; Zhiyong Qi; Yuling Chen; Kai Cheng; Haitao Yang; Mengxi Chen; Jiachen Xu; Yixuan Zhang; Yu Ren; Weiyan Liu; Danyang Lin; Guoran Huang; et al. (Remote Sensing of Environment, 2025)

Combining deep learning and protein engineering to develop a thermostable protease for aquafeed applications - Zipeng Wu; Yuling Wang; Yiran Lao; Yutong Gao; Lingjie Kong; Han Jiang; Yuyang Zou; Peizhi Gu; Mingtao Huang; Xiufang Liu; Tao Wei (Food Bioscience, 2025)

All-in-one electrochromic windows based on hydrogels containing dual redox pairs for affordable and large-scale applications - Yuling Zhu; Qi Zhao; Chenglong Mu; Yahui Liu; Yuguo Xia; Xiuling Jiao; Dairong Chen; Ting Wang (Chemical Engineering Journal, 2025)

Recombinant PD1 liposome loading nintedanib for pulmonary fibrosis therapy in mice - Qian Luo; Ying Xie; Jiarui Xu; Yuxin Ren; Shuyuan Xiong; Hongrui Zhang; Yuling Chen; Haocheng Chen; Jinling Wang; Pengyu Huang; Liyu Sun; Peishan Li; et al. (Chemical Engineering Journal, 2025)

Ether-free PDMS-based composite electrolytes with intrinsic safety, high ionic conductivity and wide electrochemical window for solid state Li-metal batteries - Chenglong Mu; Jinyan Chen; Qi Zhao; Yahui Liu; Yuling Zhu; Zhang Dai; Xina Sui; Xiuling Jiao; Dairong Chen; Ting Wang (Chemical Engineering Journal, 2025)

Microalgae-induced changes in the rhizosphere microbiome improve saline-alkali tolerance of Perilla frutescens - Yunmei Zhang; Shuiwen Luo; Xuyang Gu; Wenshan Gao; Chenxing He; Ziyi Wang; Menghang Cheng; Yuling Liang; Dandan Cao; Jianfeng Liu (Journal of Applied Phycology, 2025)

Genome-wide identification and functional analysis of the polyamine metabolism-related genes in Foxtail millet (Setaria Italica L.) - Liuan Hao; Tao Wang; Yangyang Wei; Pengtao Li; Yuling Liu; Quanwei Lu; Huawen Zou; Renhai Peng (Functional & Integrative Genomics, 2025)

Genome-wide identification and analysis of paclobutrazol-resistance gene family in cotton and the positive role of GhPRE3 in salt stress and drought stress resistance - Shuaikang Geng; Jingjing Zhai; Bingkai Cui; Huiyun Shan; Zili Liu; Jiahui Li; Cong Wang; Yuling Liu; Pengtao Li; Quanwei Lu; Zihan Xiao; Xiaoping Pan; et al. (Functional & Integrative Genomics, 2025)
Compared with other transcription factors, much less studies have been performed on paclobutrazol-resistance (PRE), a subgroup of the extensive bHLH transcription factor gene family, and the research in cotton was also limited. By utilizing the PRE genes and their conserved domains identified in Arabidopsis, a total of 23, 22, 11, and 12 PRE genes were identified from two major cultivated cotton species and their two ancestors, respectively. The cotton PRE gene family was categorized into three subgroups based on evolutionary tree analysis. Motif and intron analyses indicated that the PRE gene has remained highly conserved throughout evolution. Collinearity analysis indicated that gene duplication, particularly through fragment replication, has significantly contributed to the expansion of the cotton PRE family. An exploration of the conserved elements within the PRE gene family uncovered numerous elements associated with plant stress resistance. Additionally, cotton transcriptome and qRT-PCR analysis showed that PRE genes were associated with a variety of abiotic stresses, including salt, drought, and cold treatments. Subcellular localization experiments indicated that the GhPRE3 gene is associated with membrane proteins. Finally, we selected the GhPRE3 gene for a VIGS experiment, which revealed that under salt stress and drought stress conditions, the wilting of leaves in the GhPRE3- silenced plants was significantly more severe than that observed in the control group, with T-AOC levels notably lower and MDA levels significantly higher. Overexpression of GhPRE3 enhanced seed germination and root development in transgenic Arabidopsis thaliana under salt stress and drought stresses. This suggests that GhPRE3 plays a positive regulatory role in cotton tolerance to salt and drought stressed, providing a reference for molecular genetic breeding of cotton with salt and drought tolerance.

Genome-wide identification and functional analysis of TCX gene family and the critical role of GhTCX17 in response to drought and salt stress in cotton - Yangyang Wei; Jingjing Zhai; Shuaikang Geng; Shaoliang Zhang; Yongqing Zhao; Bingkai Cui; Huiyun Shan; Yanhua Li; Cong Wang; Pengtao Li; Yuling Liu; Quanwei Lu; et al. (Functional & Integrative Genomics, 2025)

Identification of the STY13 gene family across the entire genome and an analysis of the essential function of GhSTY13-12 in cotton’s response to abiotic stress - Shaoliang Zhang; Huiyun Shan; Xiaopei Bo; Jiahui Li; Zili Liu; Pengtao Li; Yuling Liu; Xiaojie Yang; Quanwei Lu; Sumei Wan; Renhai Peng; Yangyang Wei; et al. (Functional & Integrative Genomics, 2025)

Vagus nerve stimulation: innovative applications in the field of hand function rehabilitation - Yize Chen; Yuling Gao; Jiaqi Zhou; Shengchao Zhang; Tong Li; Zhenni Zhang; Xiaoyang Gong; Yong Liu (Cognitive Neurodynamics, 2025)

Validating recent global canopy height maps over China's forests based on UAV lidar data - Ang Chen; Kai Cheng; Yuling Chen; Zhiyong Qi; Haitao Yang; Yu Ren; Zekun Yang; Mengxi Chen; Jiachen Xu; Yixuan Zhang; Guoran Huang; Tianyu Xiang; et al. (Remote Sensing of Environment, 2025)

Fluorine-decorated rare-earth hydroxides mediated preparation of hollow low-iridium oxyfluoride for highly efficient oxygen evolution reaction catalyst - Yuling Hu; Zhen Zeng; Yun Liu; Hao Zhang; Wenjuan Shi; Zhengye Kang; Yuliang Yuan; Wei Sun; Xinlong Tian (Chemical Engineering Journal, 2025)

The impact of COVID-19 pandemic on the etiological spectrum of respiratory infections in children - Jing Wang; Yuling Han; Xiaoling Wei; Yanqin Liu; Hua Zhang; Xiang Ma (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Mitochondria-targeted NIR fluorescent probe for detection of hydrogen sulfide and its application in monitoring food freshness and bioimaging - Yiyan Huang; Zhengkuan Tan; Xiaoyu Zhang; Haichang Ding; Jing Zhang; Chunmei Jian; Yuling Zeng; Congbin Fan; Gang Liu; Shouzhi Pu (Analytica Chimica Acta, 2025)

Genome-Wide Identification of the DVR Gene Family and Expression Analysis of GDF8 Genes in Qihe Gibel Carp - Jinyan Shan; Yuling Liu; Kaiqi Lian; Xianghui Xiao; Jun Ma; Ren Ren; Xiaolong Li; Guoqiang Wei; Youyi Kuang; Renhai Peng (Fishes, 2025)
(1) Background: The BMP/GDF (Bone Morphogenetic Protein/Growth Differentiation Factor) subfamily (Decapentaplegic-Vg1-related, DVR) within the transforming growth factor beta (TGF-β) superfamily plays critical roles in governing biological developmental processes and physiological functions. (2) Methods: In this study, we systematically investigated the DVR gene family in hexaploid Qihe gibel carp (Carassius gibelio var. Qihe) through comprehensive genomic identification, phylogenetic analysis, chromosome mapping, and cis-regulatory element prediction. The experimental design for gene expression analysis involved collecting samples from multiple tissues (brain, muscle, liver, kidney, etc.) and different developmental stages (20, 45, and 60 days post hatching, dph) to examine the expression patterns of four GDF8 genes using quantitative real-time PCR (qRT-PCR). (3) Results: We identified 50 DVR members in Qihe gibel carp. Phylogenetic analysis classified the 50 DVR family members into 20 distinct protein types, with 29 BMPs (Bone Morphogenetic Proteins) and 21 GDFs (Growth Differentiation Factors) identified. All 50 DVR proteins of Qihe gibel carp have similar TGF-β domains except for four BMP1 proteins. Chromosomal localization revealed widespread distribution of DVR members across 36 chromosomes, a pattern potentially linked to the hexaploid genome of Qihe gibel carp. Genes within the same subgroup exhibited conserved intron–exon architectures and similar intron numbers; syntenic conservation within subgroups may reflect functional constraints after polyploidization, implying evolutionary pressure to maintain functional domains. Through spatiotemporal expression profiling, we uncovered functional divergence among four GDF8 (myostatin) paralogs: GDF8-1 and GDF8-2 were predominantly expressed in brain and muscle tissues (dorsal and caudal), while GDF8-3 and GDF8-4 showed hepatic, cerebral, and renal specificity. Intriguingly, all paralogs exhibited a gradual upregulation during late development (20–60 days post hatching, dph), with peak expression staggered between 45 dph (GDF8-1/2) and 60 dph (GDF8-3/4). (4) Conclusions: These findings suggest that GDF8 plays a critical regulatory role in the growth and development of Qihe gibel carp. Collectively, these results provide a foundation for further investigations into the functional roles of the DVR gene family during the ontogenetic development of this species.

A general chopping peak function for a reservoirs group flood control regulating - Zhenyu Mu; Dedi Liu; Zhenyu Wang; Yuling Zhang; Lihua Xiong; Jie Chen; Hua Chen; Jiabo Yin (Journal of Hydrology, 2025)

Preparation of Co-Ce modified sludge-based catalyst and its application in CO2 photothermal catalytic reduction - Shu Hao; Luo Xinzeng; Liu Yuling; Jia Yang; Dou Chuanchuan; Li Bo (Fuel, 2025)

Classification and identification of chicken-derived adulteration in pork patties: A multi-dimensional quality profile and machine learning-based approach - Hui Lu; Cong Yao; Lin An; Aiying Song; Feng Ling; Qiliang Huang; Yuling Cai; Yunguo Liu; Dacheng Kang (Food Control, 2025)

Deletion of ZNRF2 Exacerbates MPTP-Induced Parkinson’s Disease by Activating mTOR-Mediated Neuroinflammatory Pathways - Fanshi Zhang; Jingqing Xu; Qi Yuan; Yuling Xie; Li Zhang; Jun Zhang; Zucai Xu; Mei Liu (Molecular Neurobiology, 2025)

Untargeted lipidomic deep-profiling of human plasma via high-performance aza-Prilezhaev aziridination-LC-MS: Unraveling C C isomeric signatures of Charcot-Marie-Tooth disease - Yuling Li; Weiran Zhao; Xiang Xiang; Yunlei Hu; Xiaoqiang Zhang; Wenjian Sun; Xiaoxuan Liu (Analytica Chimica Acta, 2025)

Regulation of coagulant dosage in water treatment based on explainable integrated time-series deep learning models - Wangben Zhao; Yuling Liu; Ren Shuang; Wang Lu; Shuaishuai Li; Chenxu Zhao; Chuanchuan Dou; Hao Shu (Process Safety and Environmental Protection, 2025)

Degradation of thiamphenicol by electroactive biofilm coupled with N-MnO2 modified layer double hydroxides as cathode in microbial fuel cell - Junfeng Chen; Yuling Xu; Xinyi Zhang; Feng Lan; Yuchen Cao; Yanyan Liu; Renjun Wang; Yuewei Yang (Journal of Environmental Management, 2025)

Influence of supports in CuFe-based catalysts for hydrogenation of CO2 to ethanol - Yangqin Liu; Yuling Ma; Xin Pu; Xin Han; Lei Ye; Lingtao Kong; Jiangbing Li; Jian Zhang; Haitao Xu; Xinglong Qin; Jichang Liu (Fuel, 2025)

A copper-doped mesoporous nanoplatform with dual enzyme-mimic activities for amplified cuproptosis and immune response - Qingqing Xu; Shuaipeng Feng; Yue Cao; Yang Li; Zhu Liu; Qiuling Deng; Jiaru Lan; Donghua Di; Yuling Mao; Siling Wang; Qinfu Zhao (Chemical Engineering Journal, 2025)

TAT-T407 Mitigates Apoptosis and Cognitive Impairments Following Cerebral Ischemia Through Disruption of TRPV1-CDK5 Interaction - Qian Feng; Ying Li; Xiangru Wen; Hui Li; Chengyu Qi; Nan Wang; Guang Zhu; Yanyan Fu; Changdong Liu; Dan Liu; Zhen Zhang; Fan Yang; et al. (Molecular Neurobiology, 2025)

Assessment of Neutralizing Antibody Activity in Clinical Studies: Use of Surrogate Measurements Instead of Stand-alone Assays - Michael A. Partridge; Lynn Kamen; Bonnie Wu; Helene Solberg; Jim McNally; Lauren Stevenson; Shalini Gupta; Susana Liu; Weifeng Xu; Yuling Wu; Joleen White (The AAPS Journal, 2025)
Neutralizing antibodies (NAbs) to protein therapeutics have traditionally been assumed to be the most impactful subset of anti-drug-antibodies (ADA). NAbs can block the biotherapeutic from engaging its target impacting efficacy and may also cause serious safety events. Stand-alone NAb assays have been employed to detect neutralizing responses, often with reconfigured versions of other assays. These methods have historically been implemented in registrational trials for all molecules, and in early-stage studies for high risk biotherapeutics. However, data has demonstrated that NAb response and ADA magnitude are highly correlated. Additionally, the use of other markers to identify clinically relevant immunogenicity, such as apparent impact on pharmacokinetics (PK) or pharmacodynamics (PD), has been increasing. This manuscript reviews the available data on clinically meaningful immunogenic responses to biologics and proposes a risk-based strategy to determine if and when to employ a stand-alone NAb assay. For molecules with a high risk of safety consequences of immunogenicity (e.g., biological mimics) a NAb assay is recommended. However, for lower-safety risk molecules a stand-alone NAb assay does not enhance the interpretation of clinical data and is likely not needed. A combination of other assessments including ADA status, magnitude and persistence, PK, and PD (and efficacy) can be used as a surrogate for NAb assay data. Integration of data from all clinical evaluations is recommended by Health Authorities and can provide a more accurate overall assessment of neutralizing activity. This approach identifies clinically impactful downstream readouts of neutralizing activity without the need for a stand-alone NAb assay. Graphical Abstract

Novel EDTA modified steel slag-based catalyst for NO removal through heterogeneous Fenton processes - Lingtao Liu; Yuan Xu; Zihua Hu; Jianying Yang; Zhuyao Li; Yuling Zhu; Jianhua Ding; Jiawei Li; Feiqiang He (Journal of Hazardous Materials, 2025)

Ginger exosome-covered mesoporous polydopamine nanoplatform ameliorates liver fibrosis via antioxidation and macrophage phenotypic transformation - Junhong Zhou; Hongwei Xu; Zhu Liu; Yuling Mao; Yian Li; Liwan He; Shuaipeng Feng; Donghua Di; Siling Wang; Qinfu Zhao (Chemical Engineering Journal, 2025)

Identification and characterization of a novel halolysin from Halostella sp. PRR32 with two C-terminal extensions - Yu Jin; Juntao Ke; Yuling Hao; Aodi Zhang; Han Wu; Yue Ding; Shengda Zhao; Jing Han; Aimin Liu; Shaoxing Chen (Extremophiles, 2025)

Characteristic analysis of floc size distribution and image texture evolution in chemical coagulation process - Shuaishuai Li; Yuling Liu; Zhixiao Wang; Chuanchuan Dou; Wangben Zhao; Hao Shu (Process Safety and Environmental Protection, 2025)

Root hair: An important guest-meeting avenue for rhizobia in legume–Rhizobium symbiosis - Jingwen Xiao; Wenxu Liu; Bicong Wu; Yuling Zhang; Sha Li; En Li (Plant Science, 2025)

Study on water temperature variation trend and disturbance patterns in hydropower development section of the upper Yellow River - Chenxu Zhao; Yuling Liu; Ce Song; Zixuan Yan (Ecohydrology & Hydrobiology, 2025)

Mineral-element-chelating activity of food-derived peptides: influencing factors and enhancement strategies - Chaonan Cai; Yuting Liu; Yuling Xu; Juntao Zhang; Benmei Wei; Chengzhi Xu; Haibo Wang (Critical Reviews in Food Science and Nutrition, 2025)

Understanding citrus aroma: Changes induced by postharvest treatments of fresh fruit - Shuxun Liu; Yuling Cai; Ying Lou; Yan Zhao; Mingfeng Cao; Ping Li; Qing Gu (Postharvest Biology and Technology, 2025)

AIE-based dual-ratiometric chemosensor for detection of sulfur dioxide derivatives and viscosity and its application in food samples and biological imaging - Na Tang; Ruian Sun; Kangshuo Xu; Haichang Ding; Yuling Zeng; Yuan Ji; Gang Liu; Shouzhi Pu (Analytica Chimica Acta, 2025)

Evaluation of the freshness (TVB-N) of pork patty during storage based on PLS-DA, SVM and BP-ANN models - Hui Lu; Aiying Song; Ming Li; Xianqi Yao; Yuling Cai; Longlong Dong; Dacheng Kang; Yunguo Liu (Food Control, 2025)

How many trees are there in China? - Kai Cheng; Haitao Yang; Yuling Chen; Zekun Yang; Yu Ren; Yixuan Zhang; Danyang Lin; Weiyan Liu; Guoran Huang; Jiachen Xu; Mengxi Chen; Zhiyong Qi; et al. (Science Bulletin, 2025)

A pilot-scale study of biological activated carbon (BAC) filter for secondary effluent of petrochemical wastewater: Performance and mechanisms - Weiqing Xu; Yuling Liu; Jinkai Xue; Jie Pan; Yaozhong Zhang; Xiaopeng Qiu; Xing Zheng (Journal of Environmental Chemical Engineering, 2025)

A high-static-low-dynamic stiffness wire rope isolator with a magnetic negative stiffness device: Experiment, analytical method, and optimization - Shilong Yang; Wei Fan; Yuling Liu; Lingfei Ma; Zhengqing Chen (Engineering Structures, 2025)

Hierarchical MXene@PBA@IL nanohybrids towards high-efficiently enhance fire safety of epoxy resin - Jirui Qu; Gaoyuan Li; Biyu Huang; Haopeng Zhang; Yuling Wang; Richeng Lian; Lei Liu; Lei Yang; Baojun Li; Xilei Chen; Chuanmei Jiao (Chemical Engineering Journal, 2025)

Evaluation of Heavy Metals and Essential Minerals in the Hair of Children with Autism Spectrum Disorder and Their Association with Symptom Severity - Xulan Zhou; Xiaochun Xia; Liming Li; Yaohui Ye; Qihui Chen; Mingyue Ke; Qian Cui; Yuling He; Yiting Chen; Shaoqing Lin; Wenlong Liu; Juan Wang (Biological Trace Element Research, 2025)

N-doped carbon nanotubes encapsulated Ni3ZnC0.7 nanoparticles catalyst for peroxymonosulfate activation: Heterojunction structure and N-doping enhance electron transfer capability - Qihao Sun; Huiyuan Deng; Na Zhao; Junjie You; Zhicheng Pan; Bo Xing; Yuling Ye; Bo Lai; Xinye Yang; Xinjie Wang; Yunhui Lu; Jian Li; et al. (Chemosphere, 2025)

Strychni Semen and two alkaloidal components cause apoptosis in HK-2 cells through TRADD-MAPK/NF-κB pathway - Wenyi Tian; Yuling Li; Fengzhi Liu; Hui Liu; Chen Li; Lin Bao; Xiaodong Liang (Toxicon, 2025)

Nitrogen input alleviates the priming effects of biochar addition on soil organic carbon decomposition - Xuhui Zhou; Zhiqiang Feng; Yixian Yao; Ruiqiang Liu; Junjiong Shao; Shuxian Jia; Yining Gao; Kui Xue; Hongyang Chen; Yuling Fu; Yanghui He (Soil Biology and Biochemistry, 2025)

Coniferous wood fossils as records of paleoecology, paleoclimatology, and paleoenvironment: A review - Leon Nahuel Torres; Xiao Shi; Yuling Na; Bing Wang; Chi Tian; Wenpei Pei; Yan Liu; Jianxin Yu (Review of Palaeobotany and Palynology, 2025)

An AP2/ERF transcription factor GhERF109 negatively regulates plant growth and development in cotton - Huiyun Shi; Ghulam Qanmber; Zuoren Yang; Yuling Guo; Shuya Ma; Sheng Shu; Yujun Li; Zhongxu Lin; Fuguang Li; Zhao Liu (Plant Science, 2025)

Design and performance analysis of novel morphing wing driven by modular deployable mechanism for underwater gliders - Hongyu Wu; Xueao Liu; Yuxing Hao; Maolin Liao; Wendong Niu; Yuling Zhang; Shaoze Yan (Ocean Engineering, 2025)

Evolutionary trends and photothermal catalytic reduction performance of carbon dioxide by MOF-derived MnOx - Dou Chuanchuan; Liu Yuling; Shu Hao; Li Shuaishuai; Shi Qiyuan; Luo Xinzeng (Fuel, 2025)

Effects of long-term exposure to sulfamethoxazole on the sediments in sewage pipe: Extracellular polymeric substance, microbial communities, and antibiotic resistance genes - Yang Tao; Changfeng Zhou; Yuling Xie; Aoxi Chen; Kunyu Liu; Xin Wu; Haodong Wei; Cuiyun Liu (Journal of Environmental Chemical Engineering, 2025)

A new insight into the straw decomposition associated with minerals: Promoting straw humification and Cd immobilization - Yuling Liu; Haowei Zeng; Siduo Ding; Zhong Hu; Baiqing Tie; Si Luo (Journal of Environmental Sciences, 2025)

Constructing a low-cost total Ce(III)-based adsorbent for efficient removal and recovery of phosphate - Tao Zhang; Junle Li; Dongqing Liu; Yuling Ma; Yu Han; Sujie Shan; Kai Sun; Elena V. Zelinskaya; Aijie Wang; Hongliang Sun; Wei Wang (Chemical Engineering Journal, 2025)

Effective enhancement of ramie anaerobic continuous flow degumming by chitosan and its microbiological mechanism - Xuehui Xie; Yiting Qin; Haonan Mo; Zhuoyu Zhao; Yuling Li; Yanxue Ma; Yao Sun; Dongyang Li; Ziyi Wu; Na Liu; Qingyun Zhang; Xiaoguang Chen (Bioresource Technology, 2025)

LINC01224 promotes the Warburg effect in gastric cancer by activating the miR-486-5p/PI3K axis - Yuling Bin; Minji Liu; Rong He; Pingfei Tang; Weiming Qu; Dajun Wu; Lin Tan; Qian Wang; Peng Jiang; Hongsai Hu (In Vitro Cellular & Developmental Biology - Animal, 2025)

Nuclear factor NF-YA4a regulates salt stress tolerance and juvenile-adult phase transition in Pyrus - Yingjie Yang; Yuling Mei; Xueping Li; Ran Wang; Chunhui Ma; Jiankun Song; Zhenhua Cui; Jianlong Liu; Xiaozhi Zhou; Dingli Li (Horticulture, Environment, and Biotechnology, 2025)

Oil/water interface behavior of hesperidin methylchalcone and its application in nano-emulsions - Yuxiang Wang; Benguo Liu; Yuling Ma; Chunyan Wang; Hanjun Ma; Sheng Geng (Food Chemistry, 2025)

Collagen IV/laminin-1 coated temozolomide-prodrug hydrogel for recruiting and eradicating residual glioma cells - Yufu Zhu; Jiaqi Jin; Yang Lu; Diancheng Hang; Xuefeng Zhang; Gang Zhao; Qing Wang; Yuling Li; Hongmei Liu (Chemical Engineering Journal, 2025)

Evaluation of the efficacy of disinfectants and disinfection methods against Ascaris suum eggs - Ruisi Zhang; Maolin Lu; Hongyan Yu; Tianlu Liu; Zhiying Cui; Yuling Yang; Mengchao Zhou; Yaxian Lu; Hang Tian; Lihong Tian; Lei Han; Zhijun Hou (Veterinary Parasitology, 2024)

A novel approach to estimate land surface temperature from landsat top-of-atmosphere reflective and emissive data using transfer-learning neural network - Shuo Xu; Dongdong Wang; Shunlin Liang; Aolin Jia; Ruohan Li; Zhihao Wang; Yuling Liu (Science of The Total Environment, 2024)

Responses of suspended sludge and biofilm in a SNAD system under C/N elevation: Microbial activity, nitrogen conversion flux and molecular ecological network - Junyu Liu; Meina Hu; Mei Hu; Jiaao Wang; Tingting Zhang; Yuling Wang; Xiaohui Wang (Science of The Total Environment, 2024)

Constructing a visual detection method for coagulation effect based on image feature machine learning - Shuaishuai Li; Yuling Liu; Zhixiao Wang; Chuanchuan Dou; Wangben Zhao; Hao Shu (Journal of Water Process Engineering, 2024)

Multi-omics analyses of the mechanism for formation of key aroma-active compounds in blood orange wine fermented by Pichia kudriavzevii - Shuxun Liu; Ying Lou; Yan Zhao; Yuling Cai; Mingfeng Cao; Yixian Li; Ping Li; Qing Gu (Food Research International, 2024)

Lactobacillus plantarum LP104 improved intestinal and brain inflammation by modulating TLR4 pathway and gut flora in alcohol liver injury mice - Yue Zhang; Yuxuan Ma; Yuling Fan; Yuexin Gao; Yamei He; Yu Wang; Bo Nan; Jingsheng Liu; Xia Li; Yuhua Wang (Food Bioscience, 2024)

Low-cost Ca/Mg co-modified biochar for effective phosphorus recovery: Adsorption mechanisms, resourceful utilization, and life cycle assessment - Ming Chen; Yifan Liu; Junchao Pan; Yuling Jiang; Xueyan Zou; Yangyang Wang (Chemical Engineering Journal, 2024)

Study on the physical properties of red clay cured by different external admixtures combined with enzyme induced carbonate precipitation technology - Yu Song; Yuling Chen; Jichun Cheng; Wei Liu; Jiaqi Li; Jianwei Zhang; Junjie Zheng (Carbonates and Evaporites, 2024)

Integration of network pharmacology and transcriptomics to explore the mechanism of isoliquiritigenin in treating heart failure induced by myocardial infarction - Lingxiao Zhang; Yuling Luan; Xinyue Ding; Chenghao Yang; Lina Xing; Hui Zhang; Zongjun Liu (Toxicology and Applied Pharmacology, 2024)

A multi-perspective assessment of satellite surface Ozone products in China: Spatiotemporal variability, land cover impacts and pollution monitoring capability - Jian Wang; Yuling Du; Tianxiang Cui; Jibo Yue; Lin Sun; Haiping Si; Ping Dong; Hebing Liu; Yong Li; Lei Shi (Remote Sensing Applications: Society and Environment, 2024)

Ecological impacts of vermiculite and submerged macrophytes on sediment enzyme activity in lake restoration: Insights from the mesocosm study - Chenxu Zhao; Yuling Liu; Zixuan Yan; Wangben Zhao; Jiayu Sun (Journal of Water Process Engineering, 2024)

Comparative analysis of anaerobic degumming effects on different bast fibers from the angle of enzyme activity and microbial community structure - Yiting Qin; Xuehui Xie; Haonan Mo; Yuling Li; Xiaoguang Chen; Yanxue Ma; Zhuoyu Zhao; Hangmi Zheng; Yao Sun; Dongyang Li; Ziyi Wu; Na Liu; et al. (Journal of Cleaner Production, 2024)

Constructing a visual detection model for floc settling velocity using machine learning - Shuaishuai Li; Yuling Liu; Zhixiao Wang; Chuanchuan Dou; Wangben Zhao (Journal of Environmental Management, 2024)

Opposite effects of soil pH on bacteria and fungi β diversity in forests at a continental scale - Changjiang Huang; Yanghui He; Lingyan Zhou; Ruiqiang Liu; Hongyang Chen; Zhenggang Du; Yuling Fu; Yimin Zhu; Yuxuan Zhou; Chuansheng Wu; Guiyao Zhou; Xuhui Zhou (Journal of Environmental Management, 2024)

Design, construction and evaluation of collaborative bio-system of Vibrio fluvialis with Chlorella sorokiniana for treating actual printing and dyeing wastewater - Yuling Song; Lijun Wang; Xi Qiang; Menglin Guo; Wenhui Gu; Songcui Wu; Shan Gao; Xuehua Liu; Xiujun Xie; Quancheng Fan; Jing Zhang; Zengling Ma; et al. (Chemical Engineering Journal, 2024)

Enhanced generation and effective utilization of H2O2 for simultaneous aging of plastics in the C3N4/Vis-LED system with the addition of phenol - Xiaoman Zhang; Ting Zhang; Hongyang Guo; Shuqi Wan; Xiaodan Liu; Jianhui Sun; Yuling Zhao; Shuying Dong; Xianfa Su; Maohong Fan (Chemical Engineering Journal, 2024)

Synergistic effect of Ru single atoms and MnO2 to boost oxygen reduction/evolution activity via strong electronic interaction - Shan Liu; Taotao Zeng; Zhanglong He; Mingqing Zuo; Shuguang Chen; Yuling Liu; Zheqiong Fan; Hao He; Qingyu Kong; Zeyan Zhou; Lei Han (Chemical Engineering Journal, 2024)

Stimulation of methane production potential and alteration in community composition of methanogens following conversion of China’s coastal marshes to paddy fields - Xiaochen Yao; Weiqi Wang; Yuling Yang; Wangting Yang; Qinan Hu; Jinghao Jin; Jiaqi Liu; Yuchao Wang; Lidong Shen (CATENA, 2024)

A turn-off xanthene-based fluorescent probe for detection of cysteine and its practical application in bioimaging and food samples - Na Tang; Kangshuo Xu; Ruian Sun; Haichang Ding; Yuling Zeng; Yuan Ji; Congbin Fan; Gang Liu; Shouzhi Pu (Analytica Chimica Acta, 2024)

The shifting pattern of CO2 source sink in a subtropical urbanizing lightly eutrophic lake - Rongjie Yang; Huixing Song; Qiao Qin; Yingying Chen; Di Li; Yuling Qiu; Kezhu Lu; Yike Tan; Qingqing Chen; Xinhao Cao; Shiliang Liu (Science of The Total Environment, 2024)

A transition from arbuscular to ectomycorrhizal forests halts soil carbon sequestration during subtropical forest rewilding - Ruiqiang Liu; Xuhui Zhou; Yanghui He; Zhenggang Du; Hongyang Chen; Yuling Fu; Liqi Guo; Guiyao Zhou; Lingyan Zhou; Jie Li; Hua Chai; Changjiang Huang; et al. (Science of The Total Environment, 2024)

Effects of OSA-starch-fatty acid interactions on the structural, digestibility and release characteristics of high amylose corn starch - Mingyue Liu; Xiaoyan Wang; Yihui Li; Danni Jin; Yuling Jiang; Yong Fang; Qinlu Lin; Yongbo Ding (Food Chemistry, 2024)

Combining effects of submerged macrophytes and lanthanum-modified bentonite on sediment enzyme activity: Evidence from mesocosm study - Chenxu Zhao; Yuling Liu; Zixuan Yan; Wangben Zhao; Jiayu Sun (Chemosphere, 2024)

Effects of basic amino acids on heterocyclic amines and quality characteristics of fried beef patties at low NaCl level - Pinghua Deng; Shuang Teng; Yu Zhou; Yuling Liu; Boqun Liao; Xiaopu Ren; Yawei Zhang (Meat Science, 2024)

A pH transformable nanocarrier for gradual and precise delivery of a natural immunomodulator and chemotherapy agent to trigger tumor apoptosis - Qianwen Sun; Wei Chen; Qi Zhang; Yanqi Han; Yue Gao; Jun Ye; Hongliang Wang; Yi Zhang; Lili Gao; Yuling Liu; Yanfang Yang (Chemical Engineering Journal, 2024)

Identification of Dalbergiae Odoriferae Lignum active ingredients and potential mechanisms in the treatment of adriamycin-induced cardiotoxicity based on network pharmacology and experimental verification - Yuling Luan; Xinyue Ding; Lingxiao Zhang; Shuyan Huang; Chenghao Yang; Yueer Tang; Lina Xing; Hui Zhang; Zongjun Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Aggregation-induced electrochemiluminescence based on intramolecular charge transfer and twisted molecular conformation for label-free Immunoassay - Jinxia Liu; Wenjun Ming; Jing Zhang; Xiaobo Zhou; Yuling Qin; Li Wu (Analytica Chimica Acta, 2024)

Salicylic acid-mediated alleviation of salt stress: Insights from physiological and transcriptomic analysis in Asarum sieboldii Miq - Muhammad Haneef Kashif; Jiangxin Feng; Ruixian Dai; Yuling Fan; Yufei Xia; Zhong Liu (Chemosphere, 2024)

Effects of low-molecular-weight organic acids on the transformation and phosphate retention of iron (hydr)oxides - Yu Liang; Jing Liu; Jiezi Jin; Yuling Han; Zhiyuan Wei (Science of The Total Environment, 2024)

Fungi and bacteria trade-off mediates drought-induced reduction in wood decomposition - Shuxian Jia; Tengfeng Yuan; Yuling Fu; Josep Penuelas; Guiyao Zhou; Lingyan Zhou; Dingqin Liu; Yanghui He; Ruiqiang Liu; Xinxin Wang; Bingqian Song; Zheng Jiang; et al. (CATENA, 2024)

EVA1A reverses lenvatinib resistance in hepatocellular carcinoma through regulating PI3K/AKT/p53 signaling axis - Xiaokun Liu; Xiao Gao; Yuling Yang; Di Yang; Qingming Guo; Lianhui Li; Shunlong Liu; Wanxin Cong; Sen Lu; Lin Hou; Bin Wang; Ning Li (Apoptosis, 2024)

An aeration requirements calculating method based on BOD5 soft measurement model using deep learning and improved coati optimization algorithm - Wangben Zhao; Yuling Liu; Xing Zhou; Shuaishuai Li; Chenxu Zhao; Chuanchuan Dou; Hao Shu (Journal of Water Process Engineering, 2024)

Bi-directional association between outdoor or social activities and cognitive function: do the PM2.5 exposure catalyze the detrimental inactivity-poor cognition cycle? - Yuling Jiang; Yifei Wu; Yang Hu; Shaojie Li; Longbin Ren; Jingjing Wang; Mingzhi Yu; Rui Yang; Zhouwei Liu; Nan Zhang; Kejia Hu; Yunquan Zhang; et al. (Environmental Research, 2024)

South and Southeast Asia controls black carbon characteristics of Meili Snow Mountains in southeast Tibetan Plateau - Pengfei Chen; Shichang Kang; Yuling Hu; Tao Pu; Yajun Liu; Shijin Wang; Mukesh Rai; Ke Wang; Lekhendra Tripathee; Chaoliu Li (Science of The Total Environment, 2024)

3D visualization of oil-abundant limon flavedo layer under drying - Sara Shamim; Zhenting Wu; Yuling Tang; Jingru Jia; Chunju Liu; Haiou Wang; Fangcheng Zheng; Long Ba (Journal of Food Engineering, 2024)

Heterogeneous variations in wintertime PM2.5 sources, compositions and exposure risks at urban/suburban rural/remote rural areas in the post COVID-19/Clean-Heating period - Zhiyong Li; Zhuangzhuang Ren; Chen Liu; Zhi Ning; Jixiang Liu; Jinming Liu; Zhen Zhai; Xiaohua Ma; Lan Chen; Yuling Zhang; Longkai Bai; Shaofei Kong (Atmospheric Environment, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

The effects of canopy gaps on soil nutrient properties: a meta-analysis - Mengting Hou; Guangqi Zhang; Yuling Li; Jiaqi Xie; Lipeng Zang; Qingfu Liu; Danmei Chen; Mingzhen Sui; Yuejun He (European Journal of Forest Research, 2024)

Mycorrhizal associations relate to stable convergence in plant–microbial competition for nitrogen absorption under high nitrogen conditions - Zhenggang Du; Lingyan Zhou; Madhav P. Thakur; Guiyao Zhou; Yuling Fu; Nan Li; Ruiqiang Liu; Yanghui He; Hongyang Chen; Jie Li; Huimin Zhou; Ming Li; et al. (Global Change Biology, 2024)
Nitrogen (N) immobilization (Nim, including microbial N assimilation) and plant N uptake (PNU) are the two most important pathways of N retention in soils. The ratio of Nim to PNU (hereafter Nim:PNU ratio) generally reflects the degree of N limitation for plant growth in terrestrial ecosystems. However, the key factors driving the pattern of Nim:PNU ratio across global ecosystems remain unclear. Here, using a global data set of 1018 observations from 184 studies, we examined the relative importance of mycorrhizal associations, climate, plant, and soil properties on the Nim:PNU ratio across terrestrial ecosystems. Our results show that mycorrhizal fungi type (arbuscular mycorrhizal (AM) or ectomycorrhizal (EM) fungi) in combination with soil inorganic N mainly explain the global variation in the Nim:PNU ratio in terrestrial ecosystems. In AM fungi‐associated ecosystems, the relationship between Nim and PNU displays a weaker negative correlation ( r = −.06, p r = .25, p

Enhanced cadmium absorption and tolerance of rice epiphytic microbes by iron oxide nanoparticles - Siduo Ding; Zhong Hu; Yuling Liu; Li Li; Yuhui Zeng; Doudou Jin; Anwei Chen; Jihai Shao; Pin Su; Si Luo (International Biodeterioration & Biodegradation, 2024)

Vertical and temporal variations in activity, abundance, and composition of nitrite-driven anaerobic methanotrophs in a paddy field - Caiyu Geng; Lidong Shen; Bingjie Ren; Hechen Huang; Jinghao Jin; Wangting Yang; Evgenios Agathokleous; Jiaqi Liu; Yuling Yang; Yanan Bai; Yuzhi Song (Applied Soil Ecology, 2024)

The ameliorative effect of probiotics on diet-induced lipid metabolism disorders: A review - Yu Wang; Zhiyi Ai; Xinyue Xing; Yuling Fan; Yue Zhang; Bo Nan; Xia Li; Yuhua Wang; Jingsheng Liu (Critical Reviews in Food Science and Nutrition, 2024)

Effects of transition-metal ions on the reduction of N-nitrosodimethylamine in water by zinc - Ying Han; Xiaoping Zheng; Beibei Jiang; Yuling Tang; Hongyuan Liu; Kemin Zhang; Yaping Guo; Jun Li (Journal of Environmental Chemical Engineering, 2024)

Mortality risk of people living with HIV under hypothetical intervention scenarios of PM2.5 and HIV severity: a prospective cohort study - Shujuan Yang; Chuanteng Feng; Teng Fei; Dan Wu; Liao Feng; Fengshun Yuan; Yao Fu; Hua Ma; Bin Yu; Li Liu; Yizhuo Li; Yiping Li; et al. (Science of The Total Environment, 2024)

Persulfate oxidation of norfloxacin by cobalt doped water hyacinth biochar composite: The key role of cobalt and singlet oxygen - Yunqiang Yi; Yue Fu; Yu Wang; Yuling Cai; Yifeng Liu; Zhimin Xu; Zenghui Diao (Journal of Water Process Engineering, 2024)

"Needle" hidden in silk floss: Inactivation effect and mechanism of melamine sponge loaded bismuth oxide composite copper-metal organic framework (MS/Bi2O3@Cu-MOF) as floating photocatalyst on Microcystis aeruginosa - Mengjiao Wang; Junfeng Chen; Yushan Wei; Lijun Hu; Yuling Xu; Yanyan Liu; Renjun Wang (Journal of Hazardous Materials, 2024)

Influence of aggregate characteristics on the plant growing environment of the planting concrete with SAC - Shanshan Jin; Yang Zhang; Yuling Yan; Zengmiao Xu; Aodong Li; Juan Wang; Pengfei Liu; Liuhuan Li; Zhihua Wang (Journal of Cleaner Production, 2024)

Unveiling China’s natural and planted forest spatial–temporal dynamics from 1990 to 2020 - Kai Cheng; Haitao Yang; Hongcan Guan; Yu Ren; Yuling Chen; Mengxi Chen; Zekun Yang; Danyang Lin; Weiyan Liu; Jiachen Xu; Guangcai Xu; Keping Ma; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Soil moisture drives the response of soil microbial nutrient limitation to N and P additions in an Inner Mongolian meadow steppe - Hong Xiao; Yuping Rong; Pengzhen Li; Yuling Liu (European Journal of Soil Biology, 2024)

Variations of activity and community structure of nitrite-driven anaerobic methanotrophs in soils between native and invasive species in China's coastal wetlands - Jiaqi Liu; Weiqi Wang; Lidong Shen; Yanan Bai; Wangting Yang; Yuling Yang; Jiangbing Xu; Maohui Tian; Xin Liu; Jinghao Jin; Yuzhi Song (European Journal of Soil Biology, 2024)

Drought-induced changes in rare microbial community promoted contribution of microbial necromass C to SOC in a subtropical forest - Xinxin Wang; Lingyan Zhou; Yuling Fu; Zheng Jiang; Shuxian Jia; Bingqian Song; Dingqin Liu; Xuhui Zhou (Soil Biology and Biochemistry, 2024)

Nitrogen and phosphorus additions alter foliar nutrient concentrations of dominant grass species and regulate primary productivity in an Inner Mongolian meadow steppe - Hong Xiao; Pengzhen Li; Thomas A. Monaco; Yuling Liu; Yuping Rong (Science of The Total Environment, 2024)

Research progress and trend of antibiotics degradation by electroactive biofilm: A review - Xinyi Zhang; Yuling Xu; Yanyan Liu; Yushan Wei; Feng Lan; Renjun Wang; Yuewei Yang; Junfeng Chen (Journal of Water Process Engineering, 2024)

Fabrication and characterization of polyvinyl alcohol/sodium alginate loaded carvacrol/silica hollow microspheres composite hydrogel as a colourimetric freshness indicator - Hongdan Hao; Bingchao Duan; Lidan Zhang; Lan Wang; Lingli Zhang; Yufei Wang; Yuanyuan Li; Chunmei Zhao; Guochao Jia; Yuling Li; Congjun Liu; Kui Lu (Food Bioscience, 2024)

Exploring low-carbon mulching strategies for maize and wheat on-farm: Spatial responses, factors and mitigation potential - Huihui Wei; Kaiping Zhang; Ning Chai; Yue Wang; Yuling Li; Jianjun Yang; Matthew Tom Harrison; Ke Liu; Pingxing Wan; Wenjuan Zhang; Guojun Sun; Zhansheng Li; et al. (Science of The Total Environment, 2024)

Long-term effectiveness and sustainability of EHC remediation in carbon tetrachloride-contaminated groundwater: Mechanistic understanding and practical applications - Liu Ling; Yaqiang Wei; Haobo Niu; Hang Zhao; Yuling Chen; Dan Qu; Miao Gao; Jian Chen (Journal of Cleaner Production, 2024)

The double heterostructure photocatalyst MoS2@ZIF-67/TiO2: Triumphant modification of TiO2 and efficient removal of Karenia mikimotoi - Yushan Wei; Junfeng Chen; Mengjiao Wang; Xinyi Zhang; Yuling Xu; Qingying Wei; Feng Lan; Peike Gao; Yanyan Liu; Renjun Wang (Chemical Engineering Journal, 2024)

Improving oxygen reduction reaction by cobalt iron-layered double hydroxide layer on nickel-metal organic framework as cathode catalyst in microbial fuel cell - Xinyi Zhang; Yuling Xu; Yanyan Liu; Yushan Wei; Feng Lan; Jiayu Wang; Xuemeng Liu; Renjun Wang; Yuewei Yang; Junfeng Chen (Bioresource Technology, 2024)

Well-known polypeptides of deer antler velvet with key actives: modern pharmacological advances - He Sun; Dandan Xiao; Wei Liu; Xue Li; Zhe Lin; Yong Li; Yuling Ding (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Research status and prospects of organic photocatalysts in algal inhibition and sterilization: a review - Yushan Wei; Renjun Wang; Mengjiao Wang; Lijun Hu; Xinyi Zhang; Yuling Xu; Yanyan Liu; Feng Lan; Junfeng Chen (Environmental Science and Pollution Research, 2023)

A biodegradable chitosan-based polymer for sustained nutrient release to stimulate groundwater hydrocarbon-degrading microflora - Jili Wang; Yuling Zhang; Ting Liu; Yujia Shi; Yang Ding; Yi Zhang; Weiqing Xu; Xinying Zhang; Yiliang Wang; Dong Li (Chemosphere, 2023)

Establishment of evaluation system for biological remediation on organic pollution in groundwater using slow-release agents - Xinyue Du; Xiaoran Zhang; Junfeng Liu; Ziyang Zhang; Liyuan Wu; Xiaojuan Bai; Chaohong Tan; Yongwei Gong; Yuling Zhang; Haiyan Li (Science of The Total Environment, 2023)

Research progress and prospect of metal-organic framework and covalent-organic framework for photocatalytic treatment of harmful algal blooms - Mengjiao Wang; Junfeng Chen; Yushan Wei; Lijun Hu; Yuling Xu; Yanyan Liu; Renjun Wang (Journal of Water Process Engineering, 2023)

Characterization, in vitro digestibility and release properties of starch-linoleic acid-sodium alginate composite film - Huirong Chen; Xiaoyan Wang; Danni Jin; Mingyue Liu; Xiaonian Wu; Yuling Jiang; Yong Fang; Qinlu Lin; Yongbo Ding (Food Research International, 2023)

Correction: The States of Different 5-HT Receptors Located in the Dorsal Raphe Nucleus Are Crucial for Regulating the Awakening During General Anesthesia - HaiXiang Ma; LeYuan Gu; YuLing Wang; Qing Xu; Yuanli Zhang; WeiHui Shao; Qian Yu; XiTing Lian; Lu Liu; JiaXuan Gu; Na Ji; XiaoLing Liu; et al. (Molecular Neurobiology, 2023)

The States of Different 5-HT Receptors Located in the Dorsal Raphe Nucleus Are Crucial for Regulating the Awakening During General Anesthesia - HaiXiang Ma; LeYuan Gu; YuLing Wang; Qing Xu; Yuanli Zhang; WeiHui Shao; Qian Yu; XiTing Lian; Lu Liu; JiaXuan Gu; Na Ji; XiaoLing Liu; et al. (Molecular Neurobiology, 2023)

Review: Specific storage in aquitards - Yinong Cai; Yuling Yin; Xingxing Kuang; Yinlei Hao; Junguo Liu; Chunmiao Zheng (Hydrogeology Journal, 2023)

Co-application of biochar and organic amendments on soil greenhouse gas emissions: A meta-analysis - Jia Fu; Xuhui Zhou; Yanghui He; Ruiqiang Liu; Yixian Yao; Guiyao Zhou; Hongyang Chen; Lingyan Zhou; Yuling Fu; Shahla Hosseini Bai (Science of The Total Environment, 2023)

Structural comparison and expression function analysis of BF/C2 in Ctenopharyngodon idella and Squaliobarbus curriculus - Yuling Wei; Zhao Lv; Qiaolin Liu; Jianbo Yu; Yu Xiao; Zongjun Du; Tiaoyi Xiao (Fish & Shellfish Immunology, 2023)

Transformation of sulfur in the sediment–water system of the sewage pipeline under different hydraulic retention time - Cuiyun Liu; Haodong Wei; Qi Liu; Yang Tao; Yuling Xie; Changfeng Zhou (Environmental Pollution, 2023)

Horizontal and vertical distribution of nitrate-driven anaerobic methane oxidation process in coastal wetlands under different plant species cover across southeast China - Wangting Yang; Weiqi Wang; Lidong Shen; Yanan Bai; Jiaqi Liu; Yuling Yang; Hechen Huang; Bingjie Ren (CATENA, 2023)

Two 3D Ln(III)-MOFs Based on Phosphineoxide Ligand: Synthesis, Structure Luminescent and Photocatalytic Properties - Yuling Li; Kecheng Liu; Wenmin Zhang; Yingxin Wang; Baoyu Wang; Yufei Wang; Xiaochuan Li (Journal of Fluorescence, 2023)

Long-term fertilization enhances the activity of anaerobic oxidation of methane coupled to nitrate reduction and associated microbial abundance in paddy soils - Yuling Yang; Lidong Shen; Xu Zhao; Evgenios Agathokleous; Shuwei Wang; Bingjie Ren; Wangting Yang; Jiaqi Liu; Jinghao Jin; Hechen Huang; Hongsheng Wu (Soil Biology and Biochemistry, 2023)

Relationship between carbon pool changes and environmental changes in arid and semi-arid steppe—A two decades study in Inner Mongolia, China - Hang Li; Banghui Yang; Yu Meng; Kai Liu; Shudong Wang; Dacheng Wang; Hongyan Zhang; Yuling Huang; Xingtao Liu; Dehui Li; Long Li; Xueke Li (Science of The Total Environment, 2023)

Wheat adaptation to environmental stresses under climate change: Molecular basis and genetic improvement - Hude Mao; Cong Jiang; Chunlei Tang; Xiaojun Nie; Linying Du; Yuling Liu; Peng Cheng; Yunfeng Wu; Huiquan Liu; Zhensheng Kang; Xiaojie Wang (Molecular Plant, 2023)

Straw removal or non-removal affects cadmium (Cd) accumulation in soil–rice (Oryza sativa L.) system at different ambient air Cd levels - Si Luo; Yuling Liu; Bihao Luo; Yihao Yang; Li Li; Xin Fu; Liang Peng; Qingru Zeng (Journal of Environmental Management, 2023)

Quantitative Assessment of Monitoring Natural Attenuation on Carbon Tetrachloride Reduction at a Groundwater-Contaminated Site in Eastern China - Yaqiang Wei; Weijiang Liu; Ling Liu; Haobo Niu; Lu Li; Yuling Chen; Jian Chen (Water, Air, & Soil Pollution, 2023)

Dkk-1–TNF-α crosstalk regulates MC3T3E1 pre-osteoblast proliferation and differentiation under mechanical stress through the ERK signaling pathway - Yeke Wu; Zheng Jing; Disi Deng; Jin Yan; Min Liu; Li Li; Yuling Zuo; Wenbin Wu; Qiongying Hu; Yunfei Xie (Molecular and Cellular Biochemistry, 2023)

Dysregulated PD-L2 is correlated with disease activity and inflammation in rheumatoid arthritis - Jian Xiong; Jie Yang; Yuling Sun; Yachun Chen; Yundi Guo; Cuiping Liu; Jing Sun (Immunogenetics, 2023)

High-precision simultaneous measurement of 187Os, 186Os, and 184Os using 1013 Ω amplifiers and CDDs on NTIMS - Guiqin Wang; Yuling Zeng; Liang Qi; Wengui Liu; Jifeng Xu (Analytica Chimica Acta, 2023)

Effect of agricultural carbon emissions on farmers’ health expenditure of China: evidence from the educational threshold effect - Yuling Hu; Junyin Tan; Na Zhang; Chengjie Liu (Environmental Science and Pollution Research, 2023)

Natural polysaccharide polymer network for sustained nutrient release to stimulate the activity of aromatic hydrocarbon-degrading indigenous microflora present in groundwater - Jili Wang; Yuling Zhang; Xi Wang; Siqi Yin; Ting Liu; Yujia Shi; Yang Ding; Yi Zhang; Weiqing Xu; Xinying Zhang; Yiliang Wang; Dong Li (Science of The Total Environment, 2023)

Intergenerational effects of parental [Cnmim]BF4 (n = 4, 6, 8) ionic liquids exposure on zebrafish development based on transcriptomic analysis - Yue Liu; Yanan Tian; Chenning Zhang; Xin Lu; Yuling Xue; Xinping Wang; Qiuyue Liao; Xin Li; Kai Lian; Jiaolong Huang; Jie Deng; Peng Duan (Science of The Total Environment, 2023)

Novel facile synthesis and room-temperature sintering of copper nanowires for solution-processed transparent conductive films - Qing Liu; Yibo Wu; Yong Li; Yuling Shi; Qianqian Pan; Danlong Yang; Tao Wang (Chemical Engineering Journal, 2023)

Correction to: Improving the specific activity and stability of alkaline pectinase PEL3 through SpyTag/SpyCatcher cyclization - Chao Du; Siqin Tan; Lin Liu; Yuling Zhou; Pan Wu; Guimin Zhang (Biotechnology Letters, 2023)

Examining the importance of built and natural environment factors in predicting self-rated health in older adults: An extreme gradient boosting (XGBoost) approach - Yiyi Chen; Xian Zhang; George Grekousis; Yuling Huang; Fanglin Hua; Zehan Pan; Ye Liu (Journal of Cleaner Production, 2023)

Trace N-doped manganese dioxide cooperated with Ping-pong chrysanthemum-like NiAl-layered double hydroxide on cathode for improving bioelectrochemical performance of microbial fuel cell - Yuling Xu; Xinyi Zhang; Yanyan Liu; Yushan Wei; Feng Lan; Renjun Wang; Yuewei Yang; Junfeng Chen (Bioresource Technology, 2023)

Mineral-microbial interactions in nine-year organic fertilization field experiment: a mechanism for carbon storage in saline-alkaline paddy soil - Mengmeng Chen; Yuling Zhang; Chunwei Gao; Shirong Zhang; Lu Liu; Lipeng Wu; Yuyi Li; Xiaodong Ding (Plant and Soil, 2023)

Variation of Cd and As accumulation in crops under oilseed rape–rice rotation system in response to different contaminated rice straw-return methods - Yuling Liu; Haowei Zeng; Hanglv Zhou; Shijing Zhang; Baiqing Tie; Liang Peng; Qingru Zeng; Hua Peng; Si Luo (Plant and Soil, 2023)

hsa_circ_0000417 downregulation suppresses androgen receptor expression and apoptotic signals in human foreskin fibroblasts via sponging miR-6756-5p - Junqiang Huang; Cheng Su; Pingan Lu; Xiangyou Zhao; Yuling Liu; Qike Xie; Chao Chen (Molecular Biology Reports, 2023)

Neutralizing Antibody Validation Testing and Reporting Harmonization - Heather Myler; João Pedras-Vasconcelos; Todd Lester; Francesca Civoli; Weifeng Xu; Bonnie Wu; Inna Vainshtein; Linlin Luo; Mohamed Hassanein; Susana Liu; Swarna Suba Ramaswamy; Johanna Mora; et al. (The AAPS Journal, 2023)
Evolving immunogenicity assay performance expectations and a lack of harmonized neutralizing antibody validation testing and reporting tools have resulted in significant time spent by health authorities and sponsors on resolving filing queries. A team of experts within the American Association of Pharmaceutical Scientists’ Therapeutic Product Immunogenicity Community across industry and the Food and Drug Administration addressed challenges unique to cell-based and non-cell-based neutralizing antibody assays. Harmonization of validation expectations and data reporting will facilitate filings to health authorities and are described in this manuscript. This team provides validation testing and reporting strategies and tools for the following assessments: (1) format selection; (2) cut point; (3) assay acceptance criteria; (4) control precision; (5) sensitivity including positive control selection and performance tracking; (6) negative control selection; (7) selectivity/specificity including matrix interference, hemolysis, lipemia, bilirubin, concomitant medications, and structurally similar analytes; (8) drug tolerance; (9) target tolerance; (10) sample stability; and (11) assay robustness. Graphical Abstract

Effect of amylose content and crystal type on the structure and digestibility of starch-fatty acid complex nanoparticle - Mingyue Liu; Xiaonian Wu; Xiaoyan Wang; Yuling Jiang; Zhengyu Huang; Yong Fang; Qinlu Lin; Yongbo Ding (Food Structure, 2023)

Improving the specific activity and stability of alkaline pectinase PEL3 through SpyTag/SpyCatcher cyclization - Chao Du; Siqin Tan; Lin Liu; Yuling Zhou; Pan Wu; Guimin Zhang (Biotechnology Letters, 2023)

Synthesis of Cu-Ce-BTC catalyst and its catalytic performance for denitration and synergistic mercury removal - Shu Hao; Liu Yuling; Jia Yang; Dou Chuanchuan (Journal of Environmental Chemical Engineering, 2023)

Promotional role of Co on Cu-SAPO-34 towards enhanced denitration performance and SO2 tolerance - Yuling Zheng; Yangyang Mi; Yonglong Li; Wenming Liu; Daishe Wu; Yingying Zhang; Zhenguo Li; Honggen Peng (Fuel, 2023)

Effects of a novel plant growth regulator B2 on stalk quality and grain yield of winter wheat in North China - Chuanxi Peng; Yuling Guo; Guanmin Huang; Yingru Liu; Zhaohu Li; Yuyi Zhou; Liusheng Duan (Plant and Soil, 2023)

Plant growth strategy determines the magnitude and direction of drought‐induced changes in root exudates in subtropical forests - Zheng Jiang; Yuling Fu; Lingyan Zhou; Yanghui He; Guiyao Zhou; Peter Dietrich; Jilan Long; Xinxin Wang; Shuxian Jia; Yuhuang Ji; Zhen Jia; Bingqian Song; et al. (Global Change Biology, 2023)
Root exudates are an important pathway for plant–microbial interactions and are highly sensitive to climate change. However, how extreme drought affects root exudates and the main components, as well as species‐specific differences in response magnitude and direction, are poorly understood. In this study, root exudation rates of total carbon (C) and its components (e.g., sugar, organic acid, and amino acid) were measured under the control and extreme drought treatments (i.e., 70% throughfall reduction) by in situ collection of four tree species with different growth rates in a subtropical forest. We also quantified soil properties, root morphological traits, and mycorrhizal infection rates to examine the driving factors underlying variations in root exudation. Our results showed that extreme drought significantly decreased root exudation rates of total C, sugar, and amino acid by 17.8%, 30.8%, and 35.0%, respectively, but increased root exudation rate of organic acid by 38.6%, which were largely associated with drought‐induced changes in tree growth rates, root morphological traits, and mycorrhizal infection rates. Specifically, trees with relatively high growth rates were more responsive to drought for root exudation rates compared with those with relatively low growth rates, which were closely related to root morphological traits and mycorrhizal infection rates. These findings highlight the importance of plant growth strategy in mediating drought‐induced changes in root exudation rates. The coordinations among root exudation rates, root morphological traits, and mycorrhizal symbioses in response to drought could be incorporated into land surface models to improve the prediction of climate change impacts on rhizosphere C dynamics in forest ecosystems.

Spatio-temporal variations of activity of nitrate-driven anaerobic oxidation of methane and community structure of Candidatus Methanoperedens-like archaea in sediment of Wuxijiang river - Haixiang Cheng; Yuling Yang; Yefan He; Xugang Zhan; Yan Liu; Zhengfeng Hu; Hechen Huang; Xiaochen Yao; Wangting Yang; Jinghao Jin; Bingjie Ren; Jiaqi Liu; et al. (Chemosphere, 2023)

Effects of land-use change on carbon emission and its driving factors in Shaanxi Province from 2000 to 2020 - Chenxu Zhao; Yuling Liu; Zixuan Yan (Environmental Science and Pollution Research, 2023)

Migration detection of six aromatic amines in polyamide food contact materials by HPLC after molecularly imprinted polymer pipette tip solid phase extraction - Yang Liu; Xueping Dang; Shicheng Zhang; Yuling Hu; Huaixia Chen (Food Packaging and Shelf Life, 2023)

Effects of abrupt and gradual increase of atmospheric CO2 concentration on methanotrophs in paddy fields - Lidong Shen; Bingjie Ren; Yuhan Jin; Xin Liu; Jinghao Jin; Hechen Huang; Maohui Tian; Wangting Yang; Yuling Yang; Jiaqi Liu; Caiyu Geng; Yanan Bai; et al. (Environmental Research, 2023)

Inhibition mechanisms of urea combined with nitrification on cadmium uptake by rice (Oryza sativa L.) seedlings - Li Li; Yuling Liu; Shijing Zhang; Siduo Ding; Xin Fu; Qingru Zeng; Liang Peng; Si Luo (Plant and Soil, 2023)

Large-scale metabolome analysis reveals dynamic changes of metabolites during foxtail millet grain filling - Tao Wang; Lu Xing; Hui Song; Yangyang Wei; Pengtao Li; Quanwei Lu; Nan Hu; Yuling Liu; Yongqing Zhao; Jinrong Liu; Baohong Zhang; Renhai Peng (Food Research International, 2023)

Characterization of the lipidomic profile of clam Meretrix petechialis in response to Vibrio parahaemolyticus infection - Shujing Zhang; Shuang Jiao; Dongwu Liu; Changjian Xie; Yuling Dong; Kang Zheng; Baozhong Liu; Qiuxiang Pang (Fish & Shellfish Immunology, 2023)

A negative-response strain sensor towards wearable microclimate changes for body area sensing networks - Jing Liu; Junze Zhang; Zeyu Zhao; Yanping Liu; Wai Cheong Tam; Zhaozhu Zheng; Xiaoqin Wang; Yuling Li; Zekun Liu; Yi Li; Gang Li (Chemical Engineering Journal, 2023)

Assessing the influence of contaminated rice straw decomposition on the speciation of cadmium and arsenic in a naturally contaminated soil - Yuling Liu; Haowei Zeng; Hanglv Zhou; Shijing Zhang; Baiqing Tie; Qingru Zeng; Anwei Chen; Si Luo (Journal of Soils and Sediments, 2023)

Pollution in river tributaries restricts the water quality of ecological water replenishment in the Baiyangdian watershed, China - Xu Yao; Zheng Wang; Wei Liu; Yao Zhang; Tianhe Wang; Yuling Li (Environmental Science and Pollution Research, 2023)

Estimating the prevalence of hypertension in 164 cities in China by wastewater-based epidemiology - Chenzhi Hou; Yuling Zhong; Lan Zhang; Muyuan Liu; Fang Yan; Mengyi Chen; Youmei Wang; Peng Xu; Mengxiang Su; Chi Hu; Bin Di (Journal of Hazardous Materials, 2023)

Mechanism of thermally activated sodium persulfate–biochar skeleton treatment to improve the dewaterability of waste activated sludge - Shuaishuai Li; Yuling Liu; Chuanchuan Dou; Ruihao Sun (Journal of Environmental Chemical Engineering, 2023)

Interaction mechanism between zein and β-lactoglobulin: Insights from multi-spectroscopy and molecular dynamics simulation methods - Chengzhi Liu; Nan Lv; Yuling Song; Lijuan Dong; Min Huang; Qing Shen; Gerui Ren; Ruibo Wu; Binju Wang; Zexing Cao; Hujun Xie (Food Hydrocolloids, 2023)

Novel sensor array distinguishes heavy metal ions based on multiple fluorescence channels from dendritic mesoporous silica nanoparticles - Xiaotong Wu; Lei Tan; Yuling Li; Wanqiong Liu; Zhihua Peng; Yanshan Dong; Zeyu Huang; Lin Zhang; Yong Liang (Analytica Chimica Acta, 2023)

A review on identification, quantification, and transformation of active species in SCR by EPR spectroscopy - Chenchen Zhang; Xinyu Liu; Meijia Jiang; Yuling Wen; Jia Zhang; Guangren Qian (Environmental Science and Pollution Research, 2023)

Comparing the indigenous microorganism system in typical petroleum-contaminated groundwater - Jili Wang; Yuling Zhang; Yang Ding; Hewei Song; Ting Liu; Yi Zhang; Weiqing Xu; Yujia Shi (Chemosphere, 2023)

Four decades of hydrological response to vegetation dynamics and anthropogenic factors in the Three-North Region of China and Mongolia - Dehui Li; Kai Liu; Shudong Wang; Taixia Wu; Hang Li; Yong Bo; Hongyan Zhang; Yuling Huang; Xueke Li (Science of The Total Environment, 2023)

Activated abscisic acid pathway and C4 pathway, inhibited cell cycle progression, responses of Ulva prolifera to short term high temperature elucidated by multi-omics - Hui Zhao; Xuanhong Liu; Ting Jiang; Chuner Cai; Kai Gu; Yuling Liu; Peimin He (Marine Environmental Research, 2023)

Photocatalytic degradation effect and mechanism of Karenia mikimotoi by non-noble metal modified TiO2 loading onto copper metal organic framework (SNP-TiO2@Cu-MOF) under visible light - Lijun Hu; Junfeng Chen; Yushan Wei; Mengjiao Wang; Yuling Xu; Chao Wang; Peike Gao; Yanyan Liu; Chunchen Liu; Yuhao Song; Ning Ding; Xiaomei Liu; et al. (Journal of Hazardous Materials, 2023)

Heterogeneous interfacial photocatalysis for the inactivation of Karenia mikimotoi by Bi2O3 loaded onto a copper metal organic framework (Bi2O3@Cu-MOF) under visible light - Mengjiao Wang; Junfeng Chen; Lijun Hu; Yushan Wei; Yuling Xu; Chao Wang; Peike Gao; Yanyan Liu; Chunchen Liu; Yuhao Song; Ning Ding; Xiaomei Liu; et al. (Chemical Engineering Journal, 2023)

Corrigendum to “Novel diketopyrrolopyrrole NIR-II fluorophores and DDR inhibitors for in vivo Chemo-photodynamic therapy of Osteosarcoma” [Chem. Eng. J. 446 (2022) 136929] - Xiaoding Cheng; Chong Zhang; Kun Shen; Huifan Liu; Caihong Bai; Qihang Ding; Mengting Guan; Junzhu Wu; Zhiquan Tian; Deliang Chen; Lin Cai; Xuechuan Hong; et al. (Chemical Engineering Journal, 2023)

Synergistic effect of CoOx and Ni-Co alloy in Ni-Co/SAPO-11 catalysts for the deoxygenation of stearic acids - Dejiang Zheng; Delin Guo; Zhongxu Wang; Xiaosheng Wang; Yuling Shan; Xinmei Liu; Zifeng Yan; Shitao Yu; Yuxiang Liu (Chemical Engineering Journal, 2023)

Spatial scale transformation–based estimation model for fresh grass yield: a case study of the Xilingol Grassland, Inner Mongolia, China - Haixin Liu; Anbing Zhang; Yuling Zhao; Anzhou Zhao; Dongli Wang (Environmental Science and Pollution Research, 2023)

A critical review of research progress for metal alloy materials in hydrogen evolution and oxygen evolution reaction - Yuling Xu; Xinyi Zhang; Yanyan Liu; Renjun Wang; Yuewei Yang; Junfeng Chen (Environmental Science and Pollution Research, 2022)

Preparation of Functionalized Graphene Oxide Composite Spheres and Removal of Cu2+ and Pb2+ from Wastewater - Huining Zhang; Xingmao Liu; Lihong Tian; Yuling Tang; Zhongyu Shi; Yankui Xiao; Zhiguo Wu; Ying Zhu; Qi Guo; Zhangpu Peng (Water, Air, & Soil Pollution, 2022)

A method for evaluating drug penetration and absorption through isolated buccal mucosa with highly accuracy and reproducibility - Shuangqing Wang; Lei Liu; Saige Meng; Yuling Wang; Daofeng Liu; Zhonggao Gao; Along Zuo; Jianpeng Guo (Drug Delivery and Translational Research, 2022)

Response of potential activity, abundance and community composition of nitrite‐dependent anaerobic methanotrophs to long‐term fertilization in paddy soils - Yuling Yang; Lidong Shen; Yanan Bai; Xu Zhao; Shuwei Wang; Jiaqi Liu; Xin Liu; Maohui Tian; Wangting Yang; Jinghao Jin; Hechen Huang; Hongsheng Wu (Environmental Microbiology, 2022)
The process of nitrite‐dependent anaerobic methane oxidation (n‐damo) catalysed by Candidatus Methylomirabilis oxyfera ( M . oxyfera )‐like bacteria is a novel pathway in regulating methane (CH 4 ) emissions from paddy fields. Nitrogen fertilization is essential to improve rice yields and soil fertility; however, its effect on the n‐damo process is largely unknown. Here, the potential n‐damo activity, abundance and community composition of M . oxyfera ‐like bacteria were investigated in paddy fields under three long‐term (32 years) fertilization treatments, i.e. unfertilized control (CK), chemical fertilization (NPK) and straw incorporation with chemical fertilization (SNPK). Relative to the CK, both NPK and SNPK treatments significantly ( p M . oxyfera ‐like bacteria. The variation of soil organic carbon (OrgC) content and inorganic nitrogen content caused by the input of chemical fertilizers and straw returning were identified as the key factors affecting the potential n‐damo activity and the abundance of M . oxyfera ‐like bacteria. However, the community composition and diversity of M . oxyfera ‐like bacteria did not change significantly by the input of fertilizers. Overall, our results provide the first evidence that long‐term fertilization greatly stimulates the n‐damo process, indicating its active role in controlling CH 4 emissions from paddy fields.

Research progress of photocatalysis for algae killing and inhibition: a review - Lijun Hu; Renjun Wang; Mengjiao Wang; Yuling Xu; Chao Wang; Yanyan Liu; Junfeng Chen (Environmental Science and Pollution Research, 2022)

Activation of cadmium under simulated solar illumination and its impact on the mobility of Cd in flooded soils - Bihao Luo; Chenfeng Xiao; Yuling Liu; Li Li; Liang Peng; Qingru Zeng; Si Luo (Environmental Science and Pollution Research, 2022)

Research on Transfer Rate of Heavy Metals and Harmful Elements in Traditional Chinese Medicine Extraction and Refining Processes and Product Health Risk Assessment - Dujia Jin; Lin Li; Wujun Dong; Xiangyang Zhu; Xuejun Xia; Renyun Wang; Jun Ye; Ran Li; Zhihua Liu; Xueqing Xu; Lili Gao; Yuling Liu; et al. (Biological Trace Element Research, 2022)

Effects of roasting and deodorisation on 3-monochloropropane-1, 2-diol esters, 3, 4-benzopyrene and trans fatty acids in peanut oil - Pan Gao; Yuling Zheng; Hui Liu; Wei Yang; Chuanrong Hu; Dongping He (Food Additives & Contaminants: Part A, 2022)

Analysis of allelic variants of RhMLO genes in rose and functional studies on susceptibility to powdery mildew related to clade V homologs - Peihong Fang; Paul Arens; Xintong Liu; Xin Zhang; Deepika Lakwani; Fabrice Foucher; Jérémy Clotault; Juliane Geike; Helgard Kaufmann; Thomas Debener; Yuling Bai; Zhao Zhang; et al. (Theoretical and Applied Genetics, 2021)
Key message Rose has 19 MLO genes. Of these, RhMLO1 and RhMLO2 were shown to be required for powdery mildew infection, which suggests their potential as susceptibility targets towards disease resistance. Abstract Powdery mildew, caused by Podosphaera pannosa , is one of the most serious and widespread fungal diseases for roses, especially in greenhouse-grown cut roses. It has been shown that certain MLO genes are involved in powdery mildew susceptibility and that loss of function in these genes in various crops leads to broad-spectrum, long-lasting resistance against this fungal disease. For this reason, these MLO genes are called susceptibility genes. We carried out a genome-wide identification of the MLO gene family in the Rosa chinensis genome, and screened for allelic variants among 22 accessions from seven different Rosa species using re-sequencing and transcriptome data. We identified 19 MLO genes in rose, of which four are candidate genes for functional homologs in clade V, which is the clade containing all dicot MLO susceptibility genes. We detected a total of 198 different allelic variants in the set of Rosa species and accessions, corresponding to 5–15 different alleles for each of the genes. Some diploid Rosa species shared alleles with tetraploid rose cultivars, consistent with the notion that diploid species have contributed to the formation of tetraploid roses. Among the four RhMLO genes in clade V, we demonstrated using expression study, virus-induced gene silencing as well as transient RNAi silencing that two of them, RhMLO1 and RhMLO2 , are required for infection by P. pannosa and suggest their potential as susceptibility targets for powdery mildew resistance breeding in rose.

Construction of chlorogenic acid-containing liposomes with prolonged antitumor immunity based on T cell regulation - Yun Zhang; Yanfang Yang; Jun Ye; Yue Gao; Hengfeng Liao; Junzhuo Zhou; Yu Feng; Dongdong Liu; Yingying Meng; Xiaoguang Chen; Lili Gao; Yuling Liu (Science China Life Sciences, 2021)

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Economic policy choice of governing haze pollution: evidence from global 74 countries - Feng Dong; Xiaojie Zhang; Yajie Liu; Yuling Pan; Xiaoyun Zhang; Ruyin Long; Ziyuan Sun (Environmental Science and Pollution Research, 2021)

Analysis of microbial community structure and degradation of ammonia nitrogen in groundwater in cold regions - Shuo Li; Yuling Zhang; Siqi Yin; Xi Wang; Ting Liu; Zhiqun Deng (Environmental Science and Pollution Research, 2020)

A Novel Self-Assembly Nanocrystal as Lymph Node-Targeting Delivery System: Higher Activity of Lymph Node Targeting and Longer Efficacy Against Lymphatic Metastasis - Yuling Mao; Jun Liu; Tianyu Shi; Ge Chen; Shujun Wang (AAPS PharmSciTech, 2019)

Preparation, Characterization, and Properties of Inclusion Complexes of Balofloxacin with Cyclodextrins - Xiuyun Ren; Hongyun Qian; Peixiao Tang; Yuling Tang; Yuanyuan Liu; Hongyu Pu; Man Zhang; Ludan Zhao; Hui Li (AAPS PharmSciTech, 2019)

Differential magnitude of rhizosphere effects on soil aggregation at three stages of subtropical secondary forest successions - Ruiqiang Liu; Xuhui Zhou; Jiawei Wang; Junjiong Shao; Yuling Fu; Chao Liang; Enrong Yan; Xiaoyong Chen; Xihua Wang; Shahla Hosseini Bai (Plant and Soil, 2019)

Alginate-based composites for environmental applications: a critical review - Bing Wang; Yongshan Wan; Yuling Zheng; Xinqing Lee; Taoze Liu; Zebin Yu; Jun Huang; Yong Sik Ok; Jianjun Chen; Bin Gao (Critical Reviews in Environmental Science and Technology, 2019)

Exogenous salicylic acid regulates reactive oxygen species metabolism and ascorbate–glutathione cycle in Nitraria tangutorum Bobr. under salinity stress - Yongqing Yan; Chenhui Pan; Yuling Du; Danyang Li; Wei Liu (Physiology and Molecular Biology of Plants, 2018)

Response of Vegetation Productivity to Climate Change and Human Activities in the Shaanxi–Gansu–Ningxia Region, China - Haixin Liu; Anbing Zhang; Tao Jiang; Anzhou Zhao; Yuling Zhao; Dongli Wang (Journal of the Indian Society of Remote Sensing, 2018)

Genetic dissection of wheat panicle traits using linkage analysis and a genome-wide association study - Kai Liu; Xiaoxiao Sun; Tangyuan Ning; Xixian Duan; Qiaoling Wang; Tongtong Liu; Yuling An; Xin Guan; Jichun Tian; Jiansheng Chen (Theoretical and Applied Genetics, 2018)

Genetic Dissection of Wheat Kernel Hardness Using Conditional QTL Mapping of Kernel Size and Protein-Related Traits - Xiaoxiao Sun; Tongtong Liu; Tangyuan Ning; Kai Liu; Xixian Duan; Xuerong Wang; Qiaoling Wang; Yuling An; Xin Guan; Ji-Chun Tian; Jian-Sheng Chen (Plant Molecular Biology Reporter, 2018)

Vitamin E-rich Nanoemulsion Enhances the Antitumor Efficacy of Low-Dose Paclitaxel by Driving Th1 Immune Response - Jun Ye; Wujun Dong; Yanfang Yang; Huazhen Hao; Hengfeng Liao; Bangyuan Wang; Xue Han; Yiqun Jin; Xuejun Xia; Yuling Liu (Pharmaceutical Research, 2017)

Therapeutic potential of pro-angiogenic BPC157 is associated with VEGFR2 activation and up-regulation - Ming-Jer Hsieh; Hsien-Ta Liu; Chao-Nin Wang; Hsiu-Yun Huang; Yuling Lin; Yu-Shien Ko; Jong-Shyan Wang; Vincent Hung-Shu Chang; Jong-Hwei S. Pang (Journal of Molecular Medicine, 2017)

Valosin-containing protein (VCP) promotes the growth, invasion, and metastasis of colorectal cancer through activation of STAT3 signaling - Qianfeng Fu; Yuling Jiang; Daxin Zhang; Xiuli Liu; Junfeng Guo; Jinlong Zhao (Molecular and Cellular Biochemistry, 2016)

Cloning and expression analysis of betalain biosynthesis genes in Amaranthus tricolor - Xueli Zheng; Shengcai Liu; Chunzhen Cheng; Rongfang Guo; Yukun Chen; Liyang Xie; Yuyuan Mao; Yuling Lin; Zihao Zhang; Zhongxiong Lai (Biotechnology Letters, 2016)

Study on the velocity structure of the crust in Southwest Yunnan of the north-south seismic belt—Results from the Menghai-Gengma-Lushui deep seismic sounding profile - ShuaiJun Wang; BaoJin Liu; JianShi Zhang; BaoFeng Liu; YuLing Duan; XiangHui Song; XiaoGuo Deng; CeJun Ma; YiRan Zang (Science China Earth Sciences, 2015)

A Neutralizing Antibody Assay Based on a Reporter of Antibody-Dependent Cell-Mediated Cytotoxicity - Yuling Wu; Jia J. Li; Hyun Jun Kim; Xu Liu; Weiyi Liu; Ahmad Akhgar; Michael A. Bowen; Susan Spitz; Xu-Rong Jiang; Lorin K. Roskos; Wendy I. White (The AAPS Journal, 2015)

Spatio-temporal effects of fertilization in Anhui Province, China - Qinpu Liu; Yuling Guo; John P. Giesy (Environment, Development and Sustainability, 2015)

Association between blood erythrocyte lead concentrations and hemoglobin levels in preschool children - Chunhua Liu; Xia Huo; Peng Lin; Yuling Zhang; Weiqiu Li; Xijin Xu (Environmental Science and Pollution Research, 2015)

Disruption of Circulating CD4+ T-Lymphocyte Subpopulations in Psoriasis Patients is Ameliorated by Narrow-Band UVB Therapy - Xiuxiu Wang; Guanghua Wang; Yu Gong; Yeqiang Liu; Junying Gu; Wenjuan Chen; Yuling Shi (Cell Biochemistry and Biophysics, 2015)

Phylogeography and evolution of a fungal–insect association on the T ibetan P lateau - Yongjie Zhang; Shu Zhang; Yuling Li; Shaoli Ma; Chengshu Wang; Meichun Xiang; Xin Liu; Zhiqiang An; Jianping Xu; Xingzhong Liu (Molecular Ecology, 2014)
Parasitoidism refers to a major form of interspecies interactions where parasitoids sterilize and/or kill their hosts typically before hosts reach reproductive age. However, relatively little is known about the evolutionary dynamics of parasitoidism. Here, we investigate the spatial patterns of genetic variation of Chinese cordyceps, including both the parasitoidal fungus Ophiocordyceps sinensis and its host insects. We sampled broadly from alpine regions on the Tibetan Plateau and obtained sequences on seven fungal and three insect DNA fragments from each of the 125 samples. Seven and five divergent lineages/cryptic species were identified within the fungus and host insects, respectively. Our analyses suggested that O . sinensis and host insects originated at similar geographic regions in southern Tibet/Yunnan, followed by range expansion to their current distributions. Cophylogenetic analyses revealed a complex evolutionary relationship between O. sinensis and its host insects. Significant congruence was found between host and parasite phylogenies and the time estimates of divergence were similar, raising the possibility of the occurrence of cospeciation events, but the incongruences suggested that host shifts were also prevalent. Interestingly, one fungal genotype was broadly distributed, consistent with recent gene flow. In contrast, the high‐frequency insect genotypes showed limited geographic distributions. The dominant genotypes from both the fungus and the insect hosts may represent ideal materials from which to develop artificial cultivation of this important Chinese traditional medicine. Our results demonstrate that both historical and contemporary events have played important roles in the phylogeography and evolution of the O. sinensis –ghost moth parasitoidism on the Tibetan Plateau.

Nutrient spatial pattern of the upstream, mainstream and tributaries of the Three Gorges Reservoir in China - YuLing Huang; Ping Zhang; DeFu Liu; ZhengJian Yang; DaoBin Ji (Environmental Monitoring and Assessment, 2014)

The Ph-3 gene from Solanum pimpinellifolium encodes CC-NBS-LRR protein conferring resistance to Phytophthora infestans - Chunzhi Zhang; Lei Liu; Xiaoxuan Wang; Jack Vossen; Guangcun Li; Tao Li; Zheng Zheng; Jianchang Gao; Yanmei Guo; Richard G. F. Visser; Junming Li; Yuling Bai; et al. (Theoretical and Applied Genetics, 2014)

Synthesis, Crystal Structures and Photo- and Electro-Luminescence of Copper(I) Complexes Containing Electron-Transporting Diaryl-1,3,4-Oxadiazole - Tianzhi Yu; Peng Liu; Haifang Chai; Jundan Kang; Yuling Zhao; Hui Zhang; Duowang Fan (Journal of Fluorescence, 2014)

Novel antimicrobial metabolites produced by Sika deer-associated Actinomyces sp. JN411010 - Yujiao Tang; Yanmei Wang; Zhaohui Wang; Jing Zhang; Jianchun Qin; Quankai Wang; Lihua Yang; Lingzhi Xu; Yuling Ding; Yang Guo; Hongliang Li; Jingsi Li; et al. (Natural Product Research, 2013)

Fine mapping of the Ph-3 gene conferring resistance to late blight (Phytophthora infestans) in tomato - Chunzhi Zhang; Lei Liu; Zheng Zheng; Yuyan Sun; Longxi Zhou; Yuhong Yang; Feng Cheng; Zhonghua Zhang; Xiaowu Wang; Sanwen Huang; Bingyan Xie; Yongchen Du; et al. (Theoretical and Applied Genetics, 2013)

Genetic mapping of gummy stem blight (Didymella bryoniae) resistance genes in Cucumis sativus-hystrix introgression lines - Lina Lou; Hongying Wang; Chuntao Qian; Jia Liu; Yuling Bai; Jinfeng Chen (Euphytica, 2013)

Synthesis, Crystal Structure and Photoluminescence of a Cyclometalated Iridium(III) Coumarin Complex - Tianzhi Yu; Chengcheng Zhang; Yuling Zhao; ShaoQiang Guo; Peng Liu; Wentao Li; Duowang Fan (Journal of Fluorescence, 2013)

The role of maize root size in phosphorus uptake and productivity of maize/faba bean and maize/wheat intercropping systems - YiKai Zhang; FanJun Chen; Long Li; YanHua Chen; BingRan Liu; YuLing Zhou; LiXing Yuan; FuSuo Zhang; GuoHua Mi (Science China Life Sciences, 2012)

Identification and mapping of quantitative resistance to late blight (Phytophthora infestans) in Solanum habrochaites LA1777 - Junming Li; Lei Liu; Yuling Bai; Richard Finkers; Feng Wang; Yongchen Du; Yuhong Yang; Bingyan Xie; Richard G. F. Visser; Adriaan W. van Heusden (Euphytica, 2011)

Seedling salt tolerance in tomato - Junming Li; Lei Liu; Yuling Bai; Pujuan Zhang; Richard Finkers; Yongchen Du; Richard G. F. Visser; Adriaan W. van Heusden (Euphytica, 2011)

Production of diosgenin from yellow ginger (Dioscorea zingiberensis C. H. Wright) saponins by commercial cellulase - Wei Liu; Wen Huang; WeiLing Sun; YuLing Zhu; JinRen Ni (World Journal of Microbiology and Biotechnology, 2010)

Molecular cloning, sequence and expression analysis of ZmArf2, a maize ADP-ribosylation factor - Yanyang Liu; Junzhou Li; Yuling Li; Mengguan Wei; Qingxin Cui; Qilei Wang (Molecular Biology Reports, 2010)

A gene encoding alanine racemase is involved in spore germination in Bacillus thuringiensis - Xiaohua Yan; Yuling Gai; Liang Liang; Gang Liu; Huarong Tan (Archives of Microbiology, 2007)

Global genome expression analysis of rice in response to drought and high-salinity stresses in shoot, flag leaf, and panicle - Junli Zhou; Xiangfeng Wang; Yuling Jiao; Yonghua Qin; Xigang Liu; Kun He; Chen Chen; Ligeng Ma; Jian Wang; Lizhong Xiong; Qifa Zhang; Liumin Fan; et al. (Plant Molecular Biology, 2007)

Identification and characterization of a germination operon from Bacillus thuringiensis - Yuling Gai; Gang Liu; Huarong Tan (Antonie van Leeuwenhoek, 2006)